Resin composition and molded article thereof

By reasonably formulating graft copolymers, thermoplastic resins and fatty acid compounds in the resin composition, the problem of insufficient mechanical properties in the existing resin composition is solved, and multiple performance improvements of the resin composition and its molded products are achieved.

CN119552469APending Publication Date: 2025-03-04MITSUBISHI CHEM CORP
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411726761.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-01-15
Filing Date
2021-10-25
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the existing resin composition, there is too much polylactic acid resin and too little graft copolymer, resulting in insufficient mechanical properties such as heat resistance, impact resistance and elastic modulus.

Method used

The resin composition including a graft copolymer, a thermoplastic resin and a fatty acid compound is used, which is formed by graft polymerizing a vinyl monomer with a rubbery polymer. The thermoplastic resin includes a methacrylic polymer and the fatty acid compound includes a saturated fatty acid amide compound.

Benefits of technology

The resin composition and its molded products have excellent mechanical properties, including the improvement of transparency, impact resistance, heat resistance and bending elastic modulus, while maintaining good product processing and abrasion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159390790000431
    Figure BDA0005159390790000431
  • Figure BDA0005159390790000491
    Figure BDA0005159390790000491
  • Figure HDA0005159390820000011
    Figure HDA0005159390820000011
Patent Text Reader

Abstract

The invention provides a resin composition and a molded article thereof. A resin composition according to the present invention contains a graft copolymer (A) and a thermoplastic resin (B) (excluding the graft copolymer (A) and a polylactic acid polymer (D)). ) and a fatty acid compound (C).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of the invention application with application number 202180070489.8 (international application number PCT / JP2021 / 039291), application date October 25, 2021, and invention name “Resin composition and its molded product”. Technical Field

[0002] The present invention relates to a resin composition and a molded product thereof.

[0003] This application claims priority based on Special Application No. 2020-178003 filed in Japan on October 23, 2020, Special Application No. 2021-005171 filed in Japan on January 15, 2021, and Special Application No. 2021-005172 filed in Japan on January 15, 2021, and the contents of which are incorporated herein by reference. Background Art

[0004] (Meth)acrylic resins are widely used in various fields such as optical materials, lighting materials, materials for housing equipment, building materials, and vehicle parts due to their excellent appearance, weather resistance, and dimensional stability.

[0005] In recent years, for the purpose of reducing the environmental load on the (meth)acrylic resin, there has been a demand for a resin composition containing less (meth)acrylic resin by blending a biomass resin made of a plant raw material such as a polylactic acid resin.

[0006] On the other hand, in the above-mentioned applications, (meth)acrylic resins having excellent transparency are required from the viewpoint of excellent product appearance.

[0007] In addition, in the above-mentioned applications, the products may be damaged due to contact with people, scattered objects, etc., and thus (meth)acrylic resins with excellent impact resistance are required. Furthermore, in some of the above-mentioned applications, from the viewpoint of excellent processability of the products, (meth)acrylic resins with appropriately controlled mechanical properties such as bending elastic modulus and bending stress are required while maintaining high impact resistance.

[0008] Furthermore, in recent years, (meth)acrylic resin molded products have been required to have higher performance as parts have become thinner and denser, and as one of the improvements in performance, (meth)acrylic resins having excellent heat resistance have been required.

[0009] As a method for improving this situation, Patent Documents 1 to 3 propose resin compositions containing an acrylic polymer, a polylactic acid resin, and a graft copolymer as an impact resistance improving material.

[0010] Thermoplastic resins are easy to mold and process, and are widely used in a wide range of applications, including materials for residential equipment such as washbasins, bathtubs, and flush toilets; building materials for outdoor use such as billboards, window frames, and exterior wall materials; and vehicle components such as interior and exterior materials for vehicles.

[0011] When thermoplastic resins are used for the above-mentioned applications, products may be damaged due to contact with people, scattered objects, etc., and therefore, thermoplastic resins are required to have excellent impact resistance.

[0012] Furthermore, since products may be damaged due to contact with people or objects, thermoplastic resins are required to have excellent scratch resistance.

[0013] Furthermore, thermoplastic resins are required to have excellent product processability while maintaining high impact resistance and scratch resistance.

[0014] As a method for improving the impact resistance of a thermoplastic resin, for example, Patent Documents 1 and 2 disclose methacrylic resin compositions containing a polyorganosiloxane-acrylate composite rubber graft copolymer.

[0015] Patent Document 3 discloses a methacrylic resin composition containing a graft copolymer comprising a copolymerized rubber-like polymer composed of an alkyl acrylate and a conjugated diene.

[0016] Prior art literature

[0017] Patent Literature

[0018] Patent Document 1: Japanese Patent Application Publication No. 2017-197667

[0019] Patent Document 2: International Publication No. 05 / 123831 Pamphlet

[0020] Patent Document 3: International Publication No. 05 / 085352

[0021] Patent Document 4: Japanese Patent Application Laid-Open No. 11-100484

[0022] Patent Document 5: Japanese Patent Application Publication No. 2000-327880

[0023] Patent Document 6: Japanese Patent Publication No. 7-25973 Summary of the invention

[0024] Problems to be solved by the invention

[0025] However, in the resin compositions proposed in Patent Documents 1 to 3, since the polylactic acid resin is excessive and the graft copolymer is too little, the heat resistance, impact resistance, and mechanical properties such as elastic modulus and bending stress are insufficient.

[0026] A first aspect of the present invention is to provide a resin composition having excellent mechanical properties and a molded article thereof.

[0027] The second embodiment of the present invention aims to solve these problems. That is, the second embodiment of the present invention aims to provide a resin composition and a molded product thereof having excellent transparency, impact resistance, heat resistance, bending elastic modulus, and mechanical properties of bending stress of the obtained molded product.

[0028] However, the resin compositions described in Patent Documents 4 and 5 do not provide sufficient scratch resistance for the resulting molded articles.

[0029] The resin composition described in Patent Document 6 has insufficient product processability and scratch resistance of the obtained molded article. In addition, the impact resistance is not sufficient either.

[0030] The third embodiment of the present invention aims to solve these problems. That is, the third embodiment of the present invention aims to provide a resin composition having excellent scratch resistance, impact resistance and product processability of the obtained molded article and a molded article thereof.

[0031] Methods for solving problems

[0032] The present invention has the following configurations.

[0033] The first embodiment of the present invention has the following configuration.

[0034] [1] A resin composition comprising: a graft copolymer (A), a thermoplastic resin (B) (excluding the graft copolymer (A) and the polylactic acid polymer (D)), and a fatty acid compound (C).

[0035] [2] The resin composition according to [1], wherein the graft copolymer (A) is obtained by graft polymerization of a monomer and a rubber polymer,

[0036] The rubber polymer comprises at least one selected from the group consisting of a composite rubber containing polyorganosiloxane rubber and acrylic rubber, a diene rubber, and an acrylic rubber.

[0037] The above-mentioned monomers include vinyl monomers.

[0038] [3] The resin composition according to [1] or [2], wherein the graft copolymer (A) contains a silicone-based component.

[0039] [4] The resin composition according to any one of [1] to [3], wherein the thermoplastic resin (B) comprises a (meth)acrylic polymer (B1).

[0040] [5] The resin composition according to any one of [1] to [4], wherein the fatty acid compound (C) comprises at least one selected from the group consisting of saturated fatty acid amide compounds, unsaturated fatty acid amide compounds, bisfatty acid amide compounds and hydroxymethyl fatty acid amide compounds.

[0041] [6] The resin composition according to [5], wherein the fatty acid compound (C) comprises a fatty acid amide compound.

[0042] [7] The resin composition according to [6], wherein the fatty acid amide compound comprises at least one selected from the group consisting of lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide and hydroxymethylstearic acid amide.

[0043] [8] The resin composition according to any one of [1] to [7], further comprising a polylactic acid-based polymer (D).

[0044] [9] The resin composition according to any one of [1] to [8], wherein the content of the graft copolymer (A) is preferably 10 to 80% by mass, more preferably 20 to 70% by mass, and even more preferably 30 to 60% by mass, relative to the total mass of the resin composition.

[0045]

[10] In the resin composition according to any one of [1] to [9], the content of the thermoplastic resin (B) is preferably 10 to 80% by mass, more preferably 20 to 75% by mass, and even more preferably 30 to 70% by mass, relative to the total mass of the resin composition.

[0046]

[11] According to any one of [1] to

[10] , the content of the fatty acid compound (C) is preferably 1 to 20% by mass, more preferably 1.5 to 10% by mass, and even more preferably 2 to 8% by mass, relative to the total mass of the resin composition.

[0047]

[12] The resin composition according to any one of [1] to

[11] , further comprising a polylactic acid polymer (D),

[0048] The content of the polylactic acid polymer (D) is preferably 1 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 3 to 35% by mass, based on the total mass of the resin composition.

[0049]

[13] According to the resin composition described in any one of [1] to

[12] , the gel content of the graft copolymer (A) is preferably 40% by mass to 99% by mass, more preferably 50% by mass to 95% by mass, and even more preferably 55% by mass to 90% by mass.

[0050]

[14] A molded article comprising the resin composition according to any one of [1] to

[13] .

[0051] The second embodiment of the present invention has the following configuration.

[0052] [1] A resin composition comprising more than 45 parts by mass and less than 110 parts by mass of a graft copolymer (A) obtained by graft polymerization of a vinyl monomer and a rubber polymer, relative to 100 parts by mass of a total of a polylactic acid polymer (D) and a (meth)acrylic polymer (B1) containing methyl methacrylate monomer units, wherein the graft copolymer (A) is obtained by graft polymerization of a vinyl monomer (a2) and a rubber polymer (A1) selected from the group consisting of a polyorganosiloxane-acrylic rubber, a diene rubber and an acrylic rubber.

[0053] [2] The resin composition according to [1], comprising 65 parts by mass or more and 95 parts by mass or less of the graft copolymer (A) based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1).

[0054] [3] The resin composition according to [1] or [2], wherein the polyorganosiloxane-acrylic rubber is a composite rubber comprising polyorganosiloxane and an alkyl acrylate rubber.

[0055] [4] The resin composition according to any one of [1] to [3], wherein the composition ratio of the polylactic acid polymer (D) to the (meth)acrylic acid polymer (B1) is 1 / 99 to 99 / 1 (mass ratio).

[0056] [5] The resin composition according to any one of [1] to [4], wherein the composition ratio of the polylactic acid polymer (D) to the (meth)acrylic acid polymer (B1) is 5 / 95 to 50 / 50 (mass ratio).

[0057] [6] The resin composition according to any one of [1] to [5], which contains 30% by mass or more and 70% by mass or less of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1) in total, and 30% by mass or more and 70% by mass or less of the graft copolymer (A), relative to the total mass of the resin composition.

[0058] [7] The resin composition according to any one of [1] to [6], wherein the (meth)acrylic polymer (B1) contains 50% by mass or more of methyl methacrylate monomer units.

[0059] [8] The resin composition according to any one of [1] to [7], further comprising a fatty acid compound (C).

[0060] [9] The resin composition according to [8], wherein the fatty acid compound (C) contains a compound represented by the following general formula (i) as a main component.

[0061] R-CONH2(i)

[0062] (In the formula, R is a hydrocarbon group having 10 to 25 carbon atoms which may have a substituent.)

[0063]

[10] The resin composition according to [8], wherein the fatty acid compound (C) contains at least one selected from stearic acid amide and palmitic acid amide as a main component.

[0064]

[11] The resin composition according to any one of [8] to

[10] , which contains 0.01 parts by mass or more and 10 parts by mass or less of the fatty acid compound (C) based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1).

[0065]

[12] The resin composition according to any one of [1] to

[11] , wherein the refractive index Rc of the graft copolymer (A) and the total refractive index Rab of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1) satisfy the following formula (1A).

[0066] -0.03≤Rc-Rab≤+0.03···Formula (1A)

[0067]

[13] The resin composition according to any one of [1] to [8], wherein the content of the crosslinkable monomer is 0.3 to 10% by mass in 100% by mass of the total monomers constituting the rubber polymer (A1).

[0068]

[14] A molded article obtained by molding the resin composition according to any one of [1] to

[13] .

[0069] The third embodiment of the present invention has the following configuration.

[0070] [1] A resin composition comprising: a graft copolymer (A) containing a silicone-based component, a thermoplastic resin (B), and a fatty acid compound (C).

[0071] [2] The resin composition according to [1], wherein the graft copolymer (A) is a graft copolymer obtained by graft-polymerizing a monomer containing a (meth)acrylate compound with a composite rubber (c) containing a polyorganosiloxane (a) and an alkyl acrylate rubber (b).

[0072] [3] The resin composition according to [1] or [2], wherein the fatty acid compound (C) has a melting point of 90° C. or higher.

[0073] [4] The resin composition according to any one of [1] to [3], wherein the fatty acid compound (C) has a 10% weight loss temperature of 350°C or less.

[0074] [5] The resin composition according to any one of [1] to [4], wherein the fatty acid compound (C) contains a fatty acid amide as a main component.

[0075] [6] The resin composition according to [5], wherein the fatty acid amide is represented by the following general formula (i).

[0076] R-CONH2(i)

[0077] (In the formula, R is a hydrocarbon group having 10 to 25 carbon atoms which may have a substituent.)

[0078] [7] The resin composition according to any one of [1] to [6], wherein the thermoplastic resin (B) comprises a (meth)acrylate polymer containing a repeating unit derived from a (meth)acrylate monomer.

[0079] [8] The resin composition according to [7], wherein the (meth)acrylate polymer contains 80% by mass or more of repeating units derived from a (meth)acrylate monomer relative to 100% by mass of the total mass of the (meth)acrylate polymer.

[0080] [9] According to the resin composition described in any one of [1] to [8], the graft copolymer (A) is a graft copolymer obtained by grafting 30 to 70 parts by mass of a monomer containing a (meth)acrylate compound with 30 to 70 parts by mass of a composite rubber (c), wherein the composite rubber contains 1 to 20% by mass of a polysiloxane (a) and 80 to 99% by mass of an alkyl acrylate rubber (b).

[0081]

[10] The resin composition according to any one of [1] to [9], wherein the resin composition has a gel content of 1% by mass or more.

[0082]

[11] The resin composition according to

[10] , wherein the gel content of the resin composition is 35% by mass or less.

[0083]

[12] The resin composition according to any one of [1] to

[11] , wherein the resin composition contains a graft copolymer (A) at a content ratio of 1 mass % to 50 mass % and contains a thermoplastic resin (B) at a content ratio of 50 mass % to 99 mass % relative to the total mass of the resin composition (100 mass %).

[0084]

[13] The resin composition according to any one of [1] to

[12] , wherein the resin composition contains a fatty acid compound (C) at a content ratio of 0.01 mass % to 10 mass % relative to the total mass (100 mass %) of the resin composition.

[0085]

[14] A molded article comprising the resin composition according to any one of [1] to

[13] .

[0086] Effects of the Invention

[0087] According to the present invention, a resin composition and a molded article thereof can be stably provided, wherein the obtained molded article has excellent transparency, impact resistance, heat resistance, and mechanical properties such as flexural modulus and flexural stress.

[0088] According to the present invention, a resin composition having excellent scratch resistance, impact resistance and product processability of the obtained molded article and a molded article thereof can be provided.

[0089] Such a resin composition is suitable for use in vehicle exterior materials, and building materials installed outdoors, such as billboards, window frames, and exterior wall materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 It is a schematic diagram explaining the outline of the abrasion resistance test used for evaluating the molded article in the third embodiment of the present invention. DETAILED DESCRIPTION

[0091] In the present invention, "(meth)acrylic acid" means at least one selected from "acrylic acid" and "methacrylic acid." In addition, (meth)acrylate means methacrylate or acrylate.

[0092] In the present invention, "monomer" refers to an unpolymerized compound, and "repeating unit" and "structural unit" refer to a structural unit derived from a monomer and constituting a polymer formed by polymerization of the monomer. In addition, the structural unit constituting a polymer is referred to as "-monomer unit". A "repeating unit" or "structural unit" may be a unit directly formed by a polymerization reaction, or a unit in which a part of the unit is converted into another structure by treating the polymer.

[0093] In the present invention, "mass %" indicates the content ratio of a predetermined component contained in 100 mass % of the total amount.

[0094] In the present invention, unless otherwise specified, a numerical range expressed using "to" in the present specification means a range including the numerical values ​​described before and after "to" as a lower limit and an upper limit, and "A to B" means A or more and B or less.

[0095] In the present invention, the "molded article obtained" refers to a molded article obtained by molding the resin composition of the present invention.

[0096] <Resin composition>

[0097] The resin composition in the first embodiment of the present invention contains a graft copolymer (A), a thermoplastic resin (B) (excluding the graft copolymer (A) and the polylactic acid polymer (D)), and a fatty acid compound (C).

[0098] <Graft copolymer (A)>

[0099] The resin composition in the first embodiment of the present invention contains a graft copolymer (A).

[0100] Examples of the graft copolymer (A) include the same graft copolymers as those described in the second and third embodiments of the present invention described later.

[0101] <Thermoplastic resin (B)>

[0102] The resin composition in the first embodiment of the present invention contains a thermoplastic resin (B). The thermoplastic resin (B) does not contain the graft copolymer (A) and the polylactic acid polymer (D) described below.

[0103] Examples of the thermoplastic resin (B) include the same thermoplastic resins as those described in the second and third embodiments of the present invention (B) such as the (meth)acrylic polymer (B1).

[0104] <Fatty acid compound (C)>

[0105] The resin composition in the first embodiment of the present invention contains a fatty acid compound (C).

[0106] Examples of the fatty acid compound (C) include the same fatty acid compounds as those described in the second and third embodiments of the present invention described later.

[0107] <Polylactic acid polymer (D)>

[0108] The resin composition in the first embodiment of the present invention may further contain a polylactic acid-based polymer (D), or may not contain a polylactic acid-based polymer (D).

[0109] Examples of the polylactic acid-based polymer (D) include the same polylactic acid-based polymers as those described in the second embodiment of the present invention described later.

[0110] <Other additives>

[0111] The resin composition in the first embodiment of the present invention may or may not contain additives other than the graft copolymer (A), the thermoplastic resin (B) and the fatty acid compound (C).

[0112] Examples of other additives include the same additives as those described in the second and third embodiments of the present invention described later.

[0113] When the resin composition in the first embodiment of the present invention is formed into a molded article, the Charpy impact strength measured by the method described below is preferably 5 to 50 kJ / m 2 , more preferably 10 to 45 kJ / m 2 , more preferably 20 to 40 kJ / m 2 .

[0114] When the resin composition in the first embodiment of the present invention is formed into a molded article, the deflection temperature under load measured by the method described below is preferably 50 to 100°C, more preferably 60 to 95°C, and even more preferably 70 to 90°C.

[0115] When the resin composition in the first embodiment of the present invention is formed into a molded article, the bending stress measured by the method described below is preferably 10 to 70 MPa, more preferably 15 to 60 MPa, and even more preferably 20 to 50 MPa.

[0116] When the resin composition in the first embodiment of the present invention is formed into a molded article, the flexural modulus measured by the method described below is preferably 0.5 to 2.0 MPa, more preferably 1.0 to 1.85 MPa, and even more preferably 1.5 to 1.80 MPa.

[0117] When the resin composition in the first embodiment of the present invention is formed into a molded article, the total light transmittance measured by the method described below is preferably 60 to 90%, more preferably 65 to 85%, and even more preferably 70 to 80%.

[0118] When the resin composition in the first embodiment of the present invention is formed into a molded article, the haze value measured by the method described below is preferably 5 to 55%, more preferably 10 to 50%, and even more preferably 10 to 40%.

[0119] When the resin composition in the first embodiment of the present invention is formed into a molded article, the tensile elongation measured by the method described below is preferably 20 to 50%, more preferably 25 to 45%, and even more preferably 30 to 40%.

[0120] When the resin composition in the first embodiment of the present invention is formed into a molded article, the gloss difference measured by the method described below is preferably -3.0 to 50, more preferably -2.0 to 40, and even more preferably -1.5 to 35.

[0121] <Method for producing resin composition>

[0122] The resin composition in the first embodiment of the present invention can be produced by the same method as the method for producing the resin composition described in the second and third embodiments of the present invention described later.

[0123] <Molding products>

[0124] The molded article in the first embodiment of the present invention can be produced by the same method as the method for producing the molded article described in the second and third embodiments of the present invention described later.

[0125] The molded article in the first embodiment of the present invention can be used for the same purposes as the molded articles described in the second and third embodiments of the present invention described below. Specifically, the method for producing the molded article in the first embodiment of the present invention includes injection molding the resin composition in the first embodiment of the present invention.

[0126] <Resin composition>

[0127] The resin composition in the second embodiment of the present invention contains more than 45 parts by mass and 110 parts by mass or less of the graft copolymer (A) described below, based on 100 parts by mass of the total of the polylactic acid polymer (D) described below and the (meth)acrylic polymer (B1) described below.

[0128] If the lower limit of the content of the graft copolymer (A) exceeds 45 parts by mass relative to a total of 100 parts by mass of the polylactic acid polymer (D) and the (meth) acrylic acid polymer (B1), the resulting molded article has excellent transparency, mechanical properties such as bending elastic modulus, bending stress (hereinafter referred to as "bending mechanical properties"), and impact resistance. More preferably, it is 65 parts by mass or more. On the other hand, if the upper limit of the content of the above-mentioned graft copolymer (A) is less than 110 parts by mass, the resulting molded article can maintain heat resistance well. More preferably, it is less than 95 parts by mass.

[0129] The upper limit and lower limit of the content of the graft copolymer (A) can be arbitrarily combined. For example, relative to a total of 100 parts by mass of the polylactic acid polymer (D) and the (meth) acrylic acid polymer (B1), the content of the graft copolymer (A) is 45 parts by mass or more and 110 parts by mass, and more preferably 65 parts by mass or more and 95 parts by mass or less.

[0130] The composition ratio of the polylactic acid polymer (D) to the (meth) acrylic acid polymer (B1) can be arbitrarily adjusted within the above range. For example, in general, in applications where there is a high requirement for reducing environmental load, the larger the amount of the polylactic acid polymer (D), the more preferred, and in applications where there is a high requirement for heat resistance, the larger the amount of the (meth) acrylic acid polymer (B1), the more preferred.

[0131] In the resin composition of the second embodiment of the present invention, from the perspective of excellent transparency, impact resistance, heat resistance and bending mechanical properties of the resulting molded product, the composition ratio (mass ratio) of the polylactic acid polymer (D) to the (meth)acrylic polymer (B1) is preferably 1 / 99 to 99 / 1, and more preferably 1 / 95 to 50 / 50.

[0132] The resin composition in the second embodiment of the present invention may further contain a fatty acid compound (C) described below.

[0133] The resin composition in the second embodiment of the present invention may further contain other thermoplastic resins such as polystyrene, HIPS, ABS, AS, and MS resins, polyphenylene ether resins, polycarbonate resins, polyester resins, polyacetal resins, polyvinyl chloride resins, polyethylene, polypropylene, and other polyolefin resins, within a range that does not impair the effects of the present invention.

[0134] The amount of these polymers added is preferably 10 parts by mass or less, more preferably 5 parts by mass, and most preferably 0 parts by mass, based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1).

[0135] From the perspective of the transparency, impact resistance, heat resistance and excellent bending mechanical properties of the obtained molded article, the resin composition in the second embodiment of the present invention preferably contains a total of 30% by mass or more and 70% by mass or less of polylactic acid polymer (D) and (meth) acrylic acid polymer (B1) and a graft copolymer (A) of 30% by mass or more and 70% by mass or less, relative to the gross mass (100% by mass) of the resin composition. More preferably, polylactic acid polymer (D) and (meth) acrylic acid polymer (B1) are contained in a total of 40% by mass or more and 67% by mass or less, and graft copolymer (A) of 33% by mass or more and 60% by mass or less. It is further preferred to contain a total of 50% by mass or more and 65% by mass or less of polylactic acid polymer (D) and (meth) acrylic acid polymer (B1) and a graft copolymer (A) of 35% by mass or more and 50% by mass or less.

[0136] <Polylactic acid polymer (D)>

[0137] The polylactic acid-based polymer (D) is one of the constituent components of the resin composition in the second embodiment of the present invention.

[0138] The resin composition in the second embodiment of the present invention contains the polylactic acid-based polymer (D), so that the impact resistance of the obtained molded article can be improved and the transparency can be excellent.

[0139] As the polylactic acid polymer (D) used in the present invention, polylactic acid or a lactic acid copolymer obtained by copolymerization of a lactic acid monomer and other components can be used. In addition, a mixture of these polymers can also be used.

[0140] Polylactic acid can be synthesized by a known method, for example, by direct dehydration condensation of lactic acid or ring-opening polymerization of lactic acid cyclic dimer lactide as described in Japanese Patent Application Laid-Open No. 7-33861, Japanese Patent Application Laid-Open No. 59-96123, and Polymer Research Conference Proceedings Vol. 44, pp. 3198-3199.

[0141] In the case of direct dehydration condensation, any lactic acid of L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof can be used. In addition, in the case of ring-opening polymerization, any lactide of L-lactide, D-lactide, DL-lactide, meso-lactide, or a mixture thereof can be used.

[0142] The synthesis, purification and polymerization of lactide are described in various documents such as U.S. Patent No. 4,057,537, European Patent Application No. 261,572, Polymer Bulletin, 14, 491-495 (1985), and Makromol Che AG-187, 1611-1628 (1986).

[0143] The constituent molar ratio (L / D) of the L-lactic acid unit and the D-lactic acid unit in the polylactic acid may be any one of 100 / 0 to 0 / 100. L / D is preferably 100 / 0 to 60 / 40, and more preferably 100 / 0 to 80 / 20.

[0144] Lactic acid copolymers are obtained by copolymerizing lactic acid monomers or lactide with other components that can copolymerize with them. Other components that can copolymerize include dicarboxylic acids, polyols, hydroxycarboxylic acids, lactones, etc., which have two or more ester bond-forming functional groups. Dicarboxylic acids include, for example, succinic acid, azelaic acid, sebacic acid, terephthalic acid, isophthalic acid, etc.

[0145] Examples of the polyol include aromatic polyols such as products obtained by addition reaction of ethylene oxide and bisphenol; aliphatic polyols such as ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, octanediol, glycerol, sorbitan, trimethylolpropane, and neopentyl glycol; and ether glycols such as diethylene glycol, triethylene glycol, polyethylene glycol, and polypropylene glycol.

[0146] Examples of the hydroxycarboxylic acid include glycolic acid, hydroxybutylcarboxylic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 3-hydroxyvaleric acid, 4-hydroxyvaleric acid, 6-hydroxycaproic acid, and other hydroxycarboxylic acids described in Japanese Patent Application Laid-Open No. 6-184417.

[0147] Examples of the lactone include glycolide, ε-caprolactone glycolide, ε-caprolactone, β-propiolactone, δ-butyrolactone, β- or γ-butyrolactone, pivalolactone, δ-valerolactone, and the like.

[0148] The biodegradability of the lactic acid copolymer is affected by the content of the lactic acid unit in the copolymer. Therefore, although the content of the lactic acid unit in the lactic acid copolymer depends on the copolymerization component used, it is preferably 50 mol% or more, and more preferably 70 mol% or more. The mechanical properties and biodegradability of the obtained product can be improved by the content of the lactic acid unit and the copolymerization component.

[0149] The polylactic acid polymer (D) is not particularly limited, but in the case of a crystalline polylactic acid polymer, one having a melting point of 60 to 200°C and a mass average molecular weight of 50,000 to 500,000 is generally preferred, and one having a mass average molecular weight of 100,000 to 300,000 is more preferred.

[0150] In addition, for the purpose of obtaining the same effect as when using a copolymer, polylactic acid and other aliphatic polyesters can be simply blended. In this case, the content of polylactic acid contained in the blend is preferably 50 mol% or more, and more preferably 70 mol% or more in molar conversion.

[0151] As the polylactic acid-based polymer (D), commercially available polylactic acid-based polymers can be used, and examples thereof include Ingeo biopolymers "2003D", "2500HP", "4032D", and "4043D" manufactured by NatureWorks LLC.

[0152] <(Meth)acrylic acid polymer (B1)>

[0153] The (meth)acrylic polymer (B1) is one of the constituent components of the resin composition in the second embodiment of the present invention.

[0154] The resin composition in the second embodiment of the present invention can provide a molded article having excellent heat resistance by containing the (meth)acrylic polymer (B1).

[0155] The (meth)acrylic polymer (B1) is a polymer containing a methyl methacrylate monomer unit, and a homopolymer of methyl methacrylate or a copolymer of methyl methacrylate and a monomer copolymerizable therewith can be used. When a copolymer is used, it is preferred to use a copolymer containing 50% by mass or more, preferably 70% by mass or more, and more preferably 90% by mass or more of a methyl methacrylate monomer unit.

[0156] As other monomers copolymerizable with methyl methacrylate, alkyl acrylates such as methyl acrylate, ethyl acrylate, and butyl acrylate; other alkyl methacrylates such as ethyl methacrylate and butyl methacrylate; aromatic vinyl monomers such as styrene; cyanide vinyl monomers such as acrylonitrile; cyclohexylmaleimide, phenylmaleimide, maleic anhydride, and glutaric anhydride can also be used.

[0157] Among the above monomers, a copolymer of methyl methacrylate and methyl acrylate is preferably used from the viewpoint of high transparency and heat resistance.

[0158] The method for producing the (meth)acrylic polymer (B1) is not particularly limited, and various methods such as known suspension polymerization, bulk polymerization, and emulsion polymerization can be applied. The molecular weight of the (meth)acrylic polymer (B1) is not particularly limited, but is preferably a mass average molecular weight of 40,000 to 300,000.

[0159] As the (meth)acrylic polymer (B1), a commercially available (meth)acrylic polymer can be used, and examples thereof include ACRYPET "VH", "MF", "MD", and "TN-100" manufactured by Mitsubishi Chemical Corporation.

[0160] <Graft copolymer (A)>

[0161] The graft copolymer (A) is one of the constituent components of the resin composition in the second embodiment of the present invention.

[0162] The resin composition in the second embodiment of the present invention can provide a molded article having excellent transparency and bending mechanical properties by containing the graft copolymer (A).

[0163] The graft copolymer (A) in the present invention is a copolymer obtained by graft-polymerizing a vinyl monomer (a2) and a rubber polymer (A1) of at least one selected from polyorganosiloxane-acrylic rubber, diene rubber and acrylic rubber.

[0164] The particle size of the graft copolymer (A) affects the strength and transparency.

[0165] The mass average particle size of the graft copolymer (A) in the present invention is not particularly limited, but is more preferably 10 to 700 nm.

[0166] The mass average particle size of the graft copolymer (A) can be measured by a capillary particle size distribution analyzer.

[0167] As a method for adjusting the mass average particle size of the graft copolymer (A) to a desired range, there is mentioned a method of adjusting the amount of the emulsifier used in the production of the rubber polymer (A1).

[0168] Rc-Rab, which is the difference between the refractive index Rc of the graft copolymer (A) and the total refractive index Rab of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1), affects the transparency of the resin composition.

[0169] In the resin composition of the second embodiment of the present invention, the refractive index Rc of the graft copolymer (A) and the total refractive index Rab of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1) preferably satisfy the following formula (1A).

[0170] -0.03≤Rc-Rab≤+0.03···Formula (1A)

[0171] Furthermore, it is more preferable to satisfy the following formula (2A).

[0172] -0.02≤Rc-Rab≤+0.02···Formula (2A)

[0173] The refractive index Rc of the graft copolymer (A) can be measured by an Abbe refractometer.

[0174] The total refractive index Rab of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1) is a value obtained by mixing the polylactic acid polymer and the acrylic polymer constituting the resin composition in advance at their usage ratio and measuring the refractive index thereof with an Abbe refractometer.

[0175] In order to adjust the refractive index Rc of the graft copolymer (A) and the total refractive index Rab of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1) to fall within predetermined ranges, the following method was used.

[0176] That is, for example, for a resin composition having a high content of the (meth)acrylic polymer (B1) and a high value of Rab, it is preferred to use a graft copolymer obtained by using a polyorganosiloxane-acrylic rubber having a high content ratio of acrylic rubber and acrylate rubber. In this case, when the acrylic rubber or acrylate rubber is polymerized, the refractive index Rc of the graft copolymer can be further increased by containing an aromatic vinyl monomer having a higher refractive index as a copolymer component.

[0177] On the contrary, for a resin composition having a low value of Rab, it is preferred to use a graft copolymer obtained by using a polyorganosiloxane-acrylic rubber having a high content ratio of polyorganosiloxane rubber. Furthermore, by using an alkyl (meth)acrylate having a long alkyl chain as an acrylate rubber in the polyorganosiloxane-acrylic rubber, the refractive index Rc of the graft copolymer can also be reduced. In addition, in the case of using a graft copolymer obtained by using an acrylate rubber, the refractive index Rc of the graft copolymer can be reduced by using an acrylate rubber using an alkyl (meth)acrylate having a long alkyl chain.

[0178] Furthermore, the refractive index Rc of the graft copolymer (A) can also be adjusted by adjusting the type and amount of the vinyl monomer graft-copolymerized with the rubber polymer.

[0179] By using the above-mentioned predetermined graft copolymer as the graft copolymer (A), it is possible to obtain a resin composition that provides a molded article having high transparency and excellent bending mechanical properties.

[0180] <Rubber polymer (A1)>

[0181] The rubber polymer used in the graft copolymer in the second embodiment of the present invention is at least one selected from polyorganosiloxane-acrylic rubber, diene rubber and acrylic rubber. By using these rubbers as the rubber polymer, a graft copolymer having excellent bending mechanical properties can be obtained.

[0182] (Acrylic rubber)

[0183] The acrylic rubber in the present invention is a rubber obtained by polymerizing an alkyl (meth)acrylate. The acrylic rubber is obtained by polymerizing an alkyl (meth)acrylate, a crosslinking agent (CI) as needed, and a graft cross agent (GI) as needed.

[0184] It should be noted that the acrylic rubber in the present invention does not include a diene rubber including a structural unit derived from acrylic acid ester among the diene rubbers described below.

[0185] As specific examples of (meth) alkyl acrylate, there are no particular restrictions, and methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, tridecyl acrylate, ethoxyethoxyethyl acrylate, methoxytripropylene glycol acrylate, 4-hydroxybutyl acrylate, lauryl acrylate, lauryl methacrylate, stearyl methacrylate, etc. can be cited. They can be used alone or in combination of two or more. From the perspective of strength performance, as the (meth) alkyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, lauryl acrylate, tridecyl acrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, etc. are particularly preferred. The amount of (meth) alkyl acrylate used is preferably 60% by mass or more, and more preferably 70% by mass or more, in 100% by mass of all monomers constituting the acrylic rubber.

[0186] Examples of the crosslinking agent (CI) include ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, divinylbenzene, and multifunctional methacryloyl-modified silicone. The crosslinking agent (CI) may not be used, or the amount of the crosslinking agent (CI) used is preferably 0 to 10% by mass, more preferably 0.2 to 6% by mass, and further preferably 0.4 to 3% by mass, based on 100% by mass of all monomers constituting the acrylic rubber.

[0187] As the graft cross agent (GI), a monomer having two or more functions, which has an allyl group alone or an allyl group and a (meth)acryloyl group, can be used. Examples of such monomers include allyl methacrylate, triallyl cyanurate, triallyl isocyanurate, etc. These graft cross agents (GI) also function as crosslinking agents. The amount of the graft cross agent (GI) used is preferably 0 to 10% by mass, more preferably 1 to 10% by mass, and even more preferably 2 to 10% by mass, based on 100% by mass of all monomers constituting the acrylic rubber.

[0188] The crosslinking agent (CI) and the grafting agent (GI) can be used alone or in combination of two or more.

[0189] When adjusting the acrylic rubber, an aromatic vinyl monomer may be used in combination for the purpose of adjusting the refractive index of the graft copolymer (A).

[0190] Specific examples of the aromatic vinyl monomer include styrene, α-methylstyrene, vinyltoluene, etc. The amount of the aromatic vinyl monomer used is preferably 20% by mass or less, more preferably 10% by mass or less, based on 100% by mass of all monomers constituting the acrylic rubber.

[0191] From the viewpoint of strength development, the acrylic rubber is preferably a polymer having a glass transition temperature of 0° C. or lower. Here, the glass transition temperature of the acrylic rubber is measured as a transition point of Tan δ obtained by a dynamic mechanical analyzer (DMA).

[0192] The method for producing the acrylic rubber is not particularly limited, and the acrylic rubber can be produced by a known emulsion polymerization method.

[0193] <Polysiloxane-acrylic rubber>

[0194] The polyorganosiloxane-acrylic rubber in the present invention is a rubber comprising a polyorganosiloxane rubber obtained by polymerizing an organosiloxane and the above-mentioned acrylic rubber. Preferably, the rubber is formed by the above-mentioned polyorganosiloxane rubber and the above-mentioned acrylic rubber. The polyorganosiloxane rubber is obtained by polymerizing an organosiloxane, a crosslinking agent (CII) as required, and a graft cross agent (GII) as required.

[0195] As the organosiloxane, various cyclic bodies with more than 3-membered rings can be mentioned, for example, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, trimethyltriphenylcyclotrisiloxane, tetramethyltetraphenylcyclotetrasiloxane, octaphenylcyclotetrasiloxane, etc. can be mentioned. Among them, organosiloxanes with 3 to 6-membered rings are preferably used. They are used alone or in combination of two or more. The amount of the organosiloxane used is preferably 80% by mass or more, and more preferably 90% by mass or more in 100% by mass of all monomers constituting the polyorganosiloxane rubber.

[0196] As the crosslinking agent (CII), a trifunctional or tetrafunctional silane-based crosslinking agent, for example, trimethoxymethylsilane, triethoxyphenylsilane, tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetrabutoxysilane, etc. can be cited. A tetrafunctional crosslinking agent is particularly preferred, and tetraethoxysilane is particularly preferred. The amount of the crosslinking agent (CII) used is preferably 0 to 10% by mass, more preferably 1 to 10% by mass, and further preferably 2 to 10% by mass in 100% by mass of all monomers constituting the polyorganosiloxane rubber.

[0197] Examples of the grafting agent (GII) include compounds that can form a unit represented by the following formula.

[0198] CH2=C(R 2 )-COO-(CH2) p -SiR 1 n O (3-n) / 2 (GII-1)

[0199] CH2=C(R 2 )-C6H4-SiR 1 n O (3-n) / 2 (GII-2)

[0200] CH2=CH-SiR 1 n O (3-n) / 2 (GII-3)

[0201] HS-(CH2) p -SiR 1 n O (3-n) / 2 (GII-4)

[0202] (Where R 1 is methyl, ethyl, propyl or phenyl, R 2 is a hydrogen atom or a methyl group, n is 0, 1 or 2, and p represents a number from 1 to 6.

[0203] As a compound that can form the unit of the above formula (GII-1), methacryloxysiloxane is particularly preferred. Specific examples of methacryloxysiloxane include β-methacryloxyethyldimethoxymethylsilane, γ-methacryloxypropylmethoxydimethylsilane, γ-methacryloxypropyldimethoxymethylsilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylethoxydiethylsilane, γ-methacryloxypropyldiethoxymethylsilane, and γ-methacryloxybutyldiethoxymethylsilane.

[0204] Examples of the compound that can form the unit of the formula (GII-2) include p-vinylphenyldimethoxymethylsilane.

[0205] Examples of the compound that can form the unit of the formula (GII-3) include vinylsiloxanes, and a specific example thereof includes tetramethyltetravinylcyclotetrasiloxane.

[0206] Examples of the compound that can form the unit of the formula (GII-4) include γ-mercaptopropyldimethoxymethylsilane, γ-mercaptopropylmethoxydimethylsilane, and γ-mercaptopropyldiethoxymethylsilane.

[0207] The amount of the graft cross agent (GII) used is preferably 0 to 10% by mass, more preferably 0.5 to 5% by mass, based on 100% by mass of all monomers constituting the polyorganosiloxane rubber.

[0208] The method for producing the polyorganosiloxane rubber is not particularly limited, but emulsion polymerization is preferably performed.

[0209] The manufacture of the latex of the polyorganosiloxane component, for example, can use the method described in the gazette of U.S. Patent No. 2,891,920, the gazette of U.S. Patent No. 3,294,725, etc. In the present invention, for example, it is preferably manufactured by mixing a mixed solution of an organosiloxane, a cross-linking agent (CII) and a graft cross agent (GII) as required in the presence of a sulfonic acid emulsifier such as alkylbenzene sulfonic acid and alkyl sulfonic acid, for example, using a homogenizer and water shear mixing method. Alkylbenzene sulfonic acid acts as an emulsifier for organosiloxane and also becomes a polymerization initiator, so it is suitable. At this time, if alkylbenzene sulfonic acid metal salt, alkyl sulfonic acid metal salt, etc. are used in combination, it is effective for stably maintaining the polymer when graft polymerization is carried out, so it is preferred.

[0210] As the acrylate rubber in the polyorganosiloxane-acrylic rubber, the above-mentioned acrylic rubber can be used.

[0211] From the viewpoint of transparency and strength, the ratio of the rubber components in the polyorganosiloxane-acrylic rubber is preferably within the range of 1 to 70 mass % of the polyorganosiloxane rubber and 99 to 30 mass % of the acrylic rubber (the total amount of both components is 100 mass %).

[0212] From the viewpoint of strength development, the polyorganosiloxane-acrylic rubber preferably has a gel content of 80% by mass or more as measured by toluene extraction at 90° C. for 4 hours.

[0213] The method for producing the polyorganosiloxane-acrylic rubber is not particularly limited, but preferably comprises first preparing a polyorganosiloxane rubber latex by emulsion polymerization, then impregnating particles of the polyorganosiloxane rubber latex with monomers constituting acrylic rubber, and then polymerizing the mixture.

[0214] <Diene rubber>

[0215] The diene rubber in the present invention is a rubber polymer containing a structural unit derived from a diene compound. In addition, the diene rubber may have a structural unit derived from other vinyl monomers as required. In particular, a polymer having a structural unit having a glass transition temperature of -20°C or less is preferred.

[0216] As the diene rubber, specifically, polybutadiene, styrene-butadiene copolymer, acrylate-butadiene copolymer and other butadiene rubbers, styrene-isoprene copolymer and other conjugated diene rubbers can be cited. They can be used alone or in combination of two or more. It should be noted that these butadiene rubbers can be used by monomers, and the structure of the butadiene rubber can adopt a core-shell structure. For example, it is also possible to set the butadiene rubber with polybutadiene as the core and acrylate as the shell.

[0217] The monomer (diene monomer) used as a raw material of the structural unit derived from the diene compound is not particularly limited, and examples thereof include diene monomers such as butadiene and isoprene, for example, 1,3-butadiene.

[0218] Monomers that are raw materials for the above-mentioned constituent units derived from other vinyl monomers include, for example, monofunctional monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl acrylate, tert-butyl acrylate, styrene, and acrylonitrile; and polyfunctional monomers such as divinylbenzene, ethylene glycol dimethacrylate, butanediol diacrylate, triallyl cyanurate, triallyl isocyanurate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate. They can be used alone or in combination of two or more. Among these, from the viewpoint of polymerization stability of emulsion polymerization, alkyl acrylates and / or styrene having 2 to 8 carbon atoms are preferred, alkyl acrylates and / or styrene having 3 to 6 carbon atoms are more preferred, and butyl acrylate and / or styrene are particularly preferred. They can be used alone or in combination of two or more.

[0219] Furthermore, the butadiene rubber may contain 25 wt% or less of non-diene rubber polymers such as acrylic rubbers such as polybutyl acrylate, olefin rubbers such as ethylene-propylene copolymers, and silicone rubbers such as polyorganosiloxanes in 100 wt% of the rubber polymer as required.

[0220] These may contain a structural unit derived from a crosslinking agent (CI) as needed, and a structural unit derived from a grafting agent (GI) as needed.

[0221] Examples of the crosslinking agent (CI) include ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, divinylbenzene, and multifunctional methacryloyl-modified silicone. The amount of the crosslinking agent (CI) used is preferably 0 to 10% by mass, more preferably 1 to 10% by mass, and still more preferably 2 to 10% by mass, based on 100% by mass of all monomers constituting the butadiene rubber.

[0222] As the graft cross agent (GI), a monomer having two or more functions, which has an allyl group alone or an allyl group and a (meth)acryloyl group, can be used. Examples of such monomers include allyl methacrylate, triallyl cyanurate, triallyl isocyanurate, etc. These graft cross agents (GI) also function as crosslinking agents. The amount of the graft cross agent (GI) used is preferably 0 to 10% by mass, more preferably 1 to 10% by mass, and even more preferably 2 to 10% by mass in 100% by mass of all monomers constituting the butadiene rubber.

[0223] The crosslinking agent (CI) and the grafting agent (GI) can be used alone or in combination of two or more.

[0224] When adjusting the diene rubber, an aromatic vinyl monomer may be used in combination for the purpose of adjusting the refractive index of the graft copolymer (A).

[0225] Specific examples of the aromatic vinyl monomer include styrene, α-methylstyrene, vinyltoluene, etc. The amount of the aromatic vinyl monomer used is preferably 20% by mass or less, more preferably 10% by mass or less, based on 100% by mass of all monomers constituting the butadiene rubber.

[0226] From the viewpoint of strength development, the diene rubber is preferably a polymer having a glass transition temperature of 0° C. or lower. Here, the glass transition temperature of the diene rubber is measured as a transition point of Tan δ obtained by a dynamic mechanical analyzer (DMA).

[0227] The method for producing the diene rubber is not particularly limited, and the diene rubber can be produced by a known emulsion polymerization method.

[0228] <Content of cross-linking monomer>

[0229] The content of the crosslinkable monomer in the rubber polymer (A1) affects both the strength and the bending whitening property of the resin composition. Here, the crosslinkable monomer refers to a crosslinking agent (CI, CII) and a graft crosslinking agent (GI).

[0230] The total amount of these crosslinking monomers used is preferably 0.3 to 10% by mass, more preferably 1 to 10% by mass, and still more preferably 2 to 10% by mass in the total 100% by mass of the monomers constituting the rubber polymer (A1). By making the total amount of the crosslinking monomers used within this range, it is possible to effectively suppress whitening at bends while maintaining strength.

[0231] <Graft>

[0232] The graft copolymer (A) can be obtained by graft-polymerizing the vinyl monomer (a2) in the presence of the rubber polymer (A1) described above.

[0233] The vinyl monomer (a2) is not particularly limited. Specific examples thereof include aromatic vinyl monomers such as styrene, α-methylstyrene, and vinyltoluene; methacrylates such as methyl methacrylate and 2-ethylhexyl methacrylate; acrylates such as methyl acrylate, ethyl acrylate, and n-butyl acrylate; and various vinyl monomers such as cyanide vinyl compounds such as acrylonitrile and methacrylonitrile. These vinyl monomers can be used alone or in combination of two or more.

[0234] From the perspective of strength and heat resistance, the vinyl monomer may include a crosslinking monomer. Specific examples thereof include monomers that act as crosslinking agents such as ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, divinylbenzene, and multifunctional methacryloyl-modified silicone; allyl methacrylate, triallyl cyanurate, triallyl isocyanurate, and the like.

[0235] The graft polymerization can be carried out by general dropwise polymerization. The polymerization can be carried out in one stage or in multiple stages.

[0236] <Graft copolymer (A)>

[0237] The ratio of the rubber polymer (A1) to the graft in the graft copolymer is based on a total of 100 parts by mass of the two, and the amount of the rubber polymer is preferably 60 to 99 parts by mass, and more preferably 65 to 95 parts by mass. In addition, the amount of the graft is preferably 1 to 40 parts by mass, and more preferably 5 to 30 parts by mass. If the amount of the graft portion is 1 part by mass or more, the dispersibility of the obtained graft copolymer in the resin composition becomes good, and the processability of the resin composition is improved. On the other hand, if the amount of the graft portion is 40 parts by mass or less, the strength performance of the graft copolymer is improved.

[0238] The graft copolymer (A) is usually obtained as a latex. The graft copolymer obtained as the latex is preferably recovered in the form of powder or particles by spray recovery or wet coagulation using a coagulant such as an acid or a salt. However, in the case of containing functional groups, wet coagulation using an acid is not preferred. This is because when an acid is used, the functional group is sometimes inactivated or has an adverse effect on the functional group. In addition, in the case of wet coagulation using salts, alkaline earth metal salts such as calcium acetate, calcium chloride, magnesium sulfate, etc. are preferably used. If an alkaline earth metal is used, decomposition of the matrix resin caused by moisture and heat can be suppressed as much as possible. If the degradation of the matrix resin can be suppressed, the moisture and heat resistance of the molded article formed by the resin composition is improved. Moisture and heat resistance affects the strength performance of the molded article and has a great impact on the recyclability of the molded article.

[0239] Furthermore, as a recovery method that takes recyclability into consideration, a spray recovery method that does not contain the salts used as coagulants is effective. When spray recovery is performed, in addition to the graft copolymer, fillers or other polymers can be co-sprayed at the same time and recovered in the form of a powder combined with the two. By selecting the type of co-sprayed substance, it is also possible to achieve more preferred operability of the powder properties. As the components to be co-sprayed, calcium components are representative, and silicon dioxide, hard vinyl copolymers, etc. can be cited.

[0240] <Fatty acid compound (C)>

[0241] The resin composition in the second embodiment of the present invention contains the fatty acid compound (C), thereby maintaining good transparency, impact resistance, heat resistance, and mechanical properties of flexural modulus and flexural stress of the obtained molded article, while further improving the slidability.

[0242] In the present invention, from the viewpoint of making the obtained molded article have excellent sliding properties, the fatty acid compound (C) is preferably a chain hydrocarbon compound having at least one functional group selected from a carbonyl group, a carboxyl group, an amide group and an ester group in the molecule. The chain hydrocarbon compound refers to a compound in which the carbon atom to which at least one functional group selected from a carbonyl group, a carboxyl group, an amide group and an ester group is bonded becomes a constituent atom of the carbon chain. The carbon chain in the chain hydrocarbon compound may be saturated or unsaturated, and may be straight chain or branched.

[0243] As the fatty acid compound (C), for example, as a chain hydrocarbon compound having a carboxyl group in the molecule, fatty acids and their derivatives can be cited. As a chain hydrocarbon compound having an amide group in the molecule, fatty acid amides and their derivatives can be cited. As a chain hydrocarbon compound having an ester group or a carbonyl group in the molecule, fatty acid alkyl esters and their derivatives, or fatty acid glycerides and their derivatives can be cited.

[0244] Derivatives of fatty acids, derivatives of fatty acid amides, derivatives of fatty acid alkyl esters, and derivatives of fatty acid glycerides are compounds having structures in which hydrogen atoms in chain hydrocarbon compounds or part or all of side chains are replaced with other organic groups. Examples of the organic group include polyether groups, polyalkyl groups, aralkyl groups, and polyester groups, which may be singular or in combination of two or more.

[0245] Furthermore, as the derivative of the fatty acid amide, it is possible to appropriately select and use it from various compounds such as monoamide and bisamide according to various situations.

[0246] These fatty acid compounds (C) may be used alone or in combination of two or more.

[0247] Among these fatty acid compounds (C), fatty acid amide compounds and derivatives thereof (hereinafter, these are also collectively referred to as "fatty acid amide compounds (C1)").

[0248] The fatty acid amide compound (C1) may contain a compound represented by the following general formula (i) (hereinafter also referred to as "compound (i)") as a main component. Compound (i) is preferred because even a small amount thereof can provide a molded article with excellent sliding properties and is unlikely to impair the original performance of the (meth)acrylic resin.

[0249] R-CONH2(i)

[0250] (In the general formula (i), R is a hydrocarbon group having 10 to 25 carbon atoms which may have a substituent.) Here, the term "containing as a main component" means that the above-mentioned fatty acid compound (C) contains 85.0% by mass or more of the fatty acid amide compound (C1) relative to the total mass (100% by mass) of the fatty acid compound (C).

[0251] From the viewpoint of excellent compatibility with the (meth)acrylic polymer (B1) and excellent slidability of the obtained molded article, the lower limit of the number of carbon atoms of R in the formula (i) of the fatty acid amide compound (C1) is preferably 10 or more, more preferably 15 or more, and further preferably 17 or more. From the viewpoint of good dispersibility of the fatty acid compound (C) in the resin composition and good slidability of the obtained molded article, the upper limit of the number of carbon atoms of R in the formula (i) of the fatty acid amide compound (C1) is preferably 25 or less, more preferably 24 or less, and further preferably 23 or less.

[0252] The above-mentioned preferred upper limit and preferred lower limit can be arbitrarily combined. For example, the number of carbon atoms of R in the formula (i) of the fatty acid amide compound is preferably 10-25, more preferably 15-24, and even more preferably 17-23.

[0253] The fatty acid amide compound (C1) is preferred because it tends to be excellent in compatibility with the (meth)acrylic polymer (B1), fluidity of the resin composition, and slidability of the obtained molded article.

[0254] As fatty acid amide compound (C1), for example, saturated fatty acid amide compound, unsaturated fatty acid amide compound, bis fatty acid amide compound, hydroxymethyl fatty acid amide compound can be mentioned. These fatty acid amide compounds can be used alone or in combination of two or more. In addition, among these fatty acid amide compounds (C1), the sliding property of the obtained molded article is more excellent, so it is preferably a saturated fatty acid amide compound.

[0255] Examples of the saturated fatty acid amide compound include lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide and hydroxymethylstearic acid amide.

[0256] These saturated fatty acid amide compounds may be used alone or in combination of two or more.

[0257] From the viewpoint of excellent slidability of the obtained molded article, the saturated fatty acid amide compound preferably contains either stearic acid amide or palmitic acid amide, and the saturated fatty acid amide compound preferably contains at least one selected from stearic acid amide and palmitic acid amide as a main component.

[0258] Here, the term "as a main component" means that, relative to the total mass (100 mass %) of the fatty acid compound (C), the fatty acid compound (C) contains 85.0 mass % or more of at least one selected from stearic acid amide and palmitic acid amide, or 85.0 mass % or more of the total of stearic acid amide and palmitic acid amide.

[0259] Examples of the unsaturated fatty acid amides include erucic acid amide, oleic acid amide, brassinoic acid amide, and elaidic acid amide.

[0260] These unsaturated fatty acid amide compounds may be used alone or in combination of two or more.

[0261] Among these unsaturated fatty acid amide compounds, erucic acid amide and oleic acid amide are preferred, and erucic acid amide is more preferred, from the viewpoint that the obtained molded article has excellent slidability.

[0262] Examples of the bisfatty acid amide compound include bisfatty acid amides such as methylenebisstearic acid amide, methylenebisoleic acid amide, ethylenebisstearic acid amide, and ethylenebisoleic acid amide; stearylstearic acid amide, stearylerucic acid amide, and oleylpalmitic acid amide.

[0263] These bisfatty acid amide compounds may be used alone or in combination of two or more.

[0264] The resin composition in the second embodiment of the present invention can contain 0.01 to 10 parts by mass of the fatty acid compound (C) based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1).

[0265] If the lower limit of the content of the fatty acid compound (C) exceeds 0.01 mass parts relative to a total of 100 mass parts of polylactic acid polymer (D) and (meth) acrylic acid polymer (B1), the sliding property of the obtained molded product is excellent. More preferably, it is more than 0.1 mass parts, and more preferably, it is more than 1.0 mass parts. On the other hand, if the upper limit of the content of the above-mentioned fatty acid compound (C) is less than 10 mass parts, the obtained molded product does not damage the original performance of the acrylic resin. More preferably, it is less than 5.0 mass parts, and more preferably, it is less than 3.0 mass parts.

[0266] The upper limit and lower limit of the content of the fatty acid compound (C) can be arbitrarily combined. For example, relative to a total of 100 parts by mass of the polylactic acid polymer (D) and the (meth) acrylic acid polymer (B1), the content of the fatty acid compound (C) is preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.1 parts by mass or more and 5.0 parts by mass or less, and further preferably 1.0 parts by mass or more and 3.0 parts by mass or less.

[0267] <Method for producing resin composition>

[0268] The method for manufacturing the resin composition in the second embodiment of the present invention is not particularly limited. Various mixing methods known to date can be used, and melt mixing is usually preferred. In addition, a small amount of solvent can be used as required. As the device used for mixing, an extruder, a Banbury mixer, a roller, a kneader, etc. can be cited. These devices only need to be operated intermittently or continuously. The mixing order of the components is not particularly limited.

[0269] <Other additives>

[0270] When producing the resin composition in the second embodiment of the present invention, other additives such as various conventionally known flame retardants and stabilizers may or may not be added at a desired stage such as during compounding, kneading, and molding of the thermoplastic resin, as long as the physical properties are not impaired.

[0271] The flame retardant that can be used in the resin composition in the second embodiment of the present invention is not particularly limited. If a halogen flame retardant, a phosphoric acid flame retardant, or a silicone flame retardant is used, the strength is not impaired, and high flame retardancy can be exhibited, so it is preferred. As such a flame retardant, for example, a halogen-containing compound, a phosphoric acid compound, a silicone compound, a halogen-containing organic metal salt compound, etc. can be cited.

[0272] Specific examples of flame retardants include phosphoric acid compounds such as phosphate compounds, phosphite compounds, and condensed phosphate compounds; aluminum hydroxide; antimony acid compounds such as antimony trioxide and antimony pentoxide; halogen-containing compounds such as halogen-containing phosphate compounds, halogen-containing condensed phosphate compounds, chlorinated paraffins, brominated aromatic triazines, and brominated phenyl alkyl ethers; sulfone or sulfate compounds; epoxy-based reactive flame retardants; and the like.

[0273] From the viewpoint of transparency, the amount of the flame retardant is preferably 10 parts by mass or less, more preferably 5 parts by mass, and most preferably 0 parts by mass, based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1).

[0274] Examples of the stabilizer include metal stabilizers and other stabilizers.

[0275] Examples of the metal stabilizer include lead stabilizers such as tribasic lead sulfate, dibasic lead phosphite, basic lead sulfite, and lead silicate; metal soap stabilizers derived from metals such as potassium, magnesium, barium, zinc, cadmium, and lead and fatty acids such as 2-ethylhexanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, hydroxystearic acid, oleic acid, ricinoleic acid, linoleic acid, and behenic acid; organic tin stabilizers derived from alkyl groups, ester groups, and fatty acid salts, maleates, and sulfides; Ba-Zn-based, Ca-Zn-based, Ba-Ca-Sn-based, Ca-Mg-Sn-based, Ca-Zn-Sn-based, Pb- Sn-based, Pb-Ba-Ca-based composite metal soap stabilizers; metal salt stabilizers derived from metals such as barium and zinc and branched fatty acids such as 2-ethylhexanoic acid, isodecanoic acid, trialkylacetic acid, unsaturated fatty acids such as oleic acid, ricinoleic acid, linoleic acid, alicyclic acids such as cyclopentane acid, phenol, benzoic acid, salicylic acid, and aromatic acids such as their substituted derivatives, usually two or more organic acids; metal salt liquid stabilizers formed by dissolving these stabilizers in organic solvents such as petroleum hydrocarbons, alcohols, and glycerol derivatives, and further adding phosphites, epoxy compounds, color prevention agents, transparency improvers, light stabilizers, antioxidants, anti-plateout agents, lubricants, and other stabilizing aids, etc.

[0276] Other stabilizers include epoxy compounds such as epoxy resins, epoxidized soybean oils, epoxidized vegetable oils, and epoxidized fatty acid alkyl esters; organic phosphites in which phosphorus is substituted with alkyl, aryl, cycloalkyl, alkoxy, etc., and which have diols such as propylene glycol, hydroquinone, and aromatic compounds such as bisphenol A; hindered phenols such as 2,4-di-tert-butyl-3-hydroxytoluene (BHT) and bisphenol dimerized with sulfur, methylene, etc., salicylates, benzophenones, benzotriazoles, and other ultraviolet absorbers; light stabilizers of hindered amines or nickel complex salts; ultraviolet shielding agents such as carbon black and rutile titanium oxide; polyols such as trimethylolpropane, pentaerythritol, sorbitol, and mannitol; nitrogen-containing compounds such as β-aminocrotonate, 2-phenylindole, diphenylthiourea, and dicyandiamide; sulfur-containing compounds such as dialkylthiodipropionate; ketone compounds such as acetoacetate, dehydroacetic acid, and β-diketone; organosilicon compounds; boric acid esters; and the like. These stabilizers can be used alone or in combination of two or more.

[0277] From the viewpoint of transparency, the amount of the stabilizer used is preferably 5 parts by mass or less, more preferably 2 parts by mass, and most preferably 0 parts by mass, based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1).

[0278] The resin composition in the second embodiment of the present invention may also contain processing aids, plasticizers, lubricants, flame retardants, heat resistance improvers, mold release agents, crystal nucleating agents, fluidity improvers, colorants, antistatic agents, conductivity imparting agents, surfactants, antifogging agents, antibacterial agents, etc.

[0279] As processing aids, for example, (meth)acrylate copolymers, etc. can be cited. From the viewpoint of transparency, the amount of processing aid used is preferably 15 parts by mass or less, more preferably 5 parts by mass, and most preferably 0 parts by mass, relative to 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic acid polymer (B1).

[0280] Examples of the plasticizer include alkyl esters of aromatic polybasic acids such as dibutyl phthalate, dioctyl phthalate, diisodecyl phthalate, diisononyl phthalate, diundecyl phthalate, trioctyl trimellitate, and triisooctyl trimellitate; alkyl esters of fatty acid polybasic acids such as dibutyl adipate, dioctyl adipate, diisononyl adipate, dibutyl azelate, dioctyl azelate, and diisononyl azelate; and tritolyl phosphate. Phosphate esters; polyester plasticizers such as compounds obtained by blocking the ends of polycondensates of polycarboxylic acids with molecular weights of about 600 to 8,000 such as adipic acid, azelaic acid, sebacic acid, and phthalic acid with polyols such as ethylene glycol, 1,2-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, and 1,4-butylene glycol with monohydric alcohols or monocarboxylic acids; epoxy plasticizers such as epoxidized soybean oil, epoxidized linseed oil, and epoxidized tall oil fatty acid-2-ethylhexyl ester; chlorinated paraffins, etc. From the viewpoint of transparency, the amount of the plasticizer used is preferably 30 parts by mass or less, more preferably 10 parts by mass, and most preferably 0 parts by mass, relative to a total of 100 parts by mass of the polylactic acid polymer (D) and the (meth)acrylic acid polymer (B1).

[0281] As lubricants, for example, pure hydrocarbons such as liquid paraffin, low molecular weight polyethylene, halogenated hydrocarbons, higher fatty acids, fatty acids such as oxy fatty acids, fatty acid amides, polyol esters of fatty acids such as glycerides, fatty alcohol esters of fatty acids (ester wax), metal soaps, fatty alcohols, polyols, polyglycols, polyglycerols, partial esters of fatty acids and polyols, esters such as partial esters of fatty acids and polyglycols, polyglycerols, (methyl) acrylate copolymers, etc. can be cited. As heat-resistant improvers, for example, (methyl) acrylate copolymers, imide copolymers, styrene-acrylonitrile copolymers, etc. can be cited. From the viewpoint of transparency, the amount of lubricant used is preferably less than 5 parts by mass, more preferably 1 part by mass, and most preferably 0 parts by mass relative to a total of 100 parts by mass of polylactic acid polymer (D) and (methyl) acrylic acid polymer (B1).

[0282] <Molding products>

[0283] The molded product in the second embodiment of the present invention is obtained by molding the above-mentioned resin combination. The molding method is not particularly limited, as long as the method suitable for the resin combination in the second embodiment of the present invention is selected from the known molding methods. For example, a method for molding using various molding machines such as an extruder, an injection molding machine, a blow molding machine, an inflation molding machine, and a calendering molding machine can be cited. Among these, particularly from the viewpoint of imparting high transparency, it is preferably molded by an extruder, an injection molding machine, a blow molding machine, and a calendering molding machine. In addition, the molded product once molded by the above method can be used to implement secondary processing such as bending molding and blow molding.

[0284] The molded products obtained in this way can be used, for example, in building materials, automobiles, toys, stationery and other sundries, OA equipment, home appliances, further packaging, automatic vending machines, pinball machine panels, etc., and can easily obtain molded products with excellent strength, transparency, and weather resistance, less whitening due to bending, and good appearance when the sheet or film is bent, blow molded, or vacuum molded. Therefore, it is particularly preferred to use it as a panel for packaging, automatic vending machines, pinball machines, etc.

[0285] <Resin composition>

[0286] The resin composition in the third embodiment of the present invention is a resin composition containing a graft copolymer (A) containing a silicone-based component described below (hereinafter simply referred to as "graft copolymer (A)"), a thermoplastic resin (B) described below, and a fatty acid compound (C) described below.

[0287] From the viewpoint of excellent impact resistance of the obtained molded article, the lower limit of the content ratio of the graft copolymer (A) contained in the resin composition in the third embodiment of the present invention is preferably 1% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more, relative to the total mass 100% by mass of the above-mentioned resin composition. On the other hand, from the viewpoint that the obtained molded article does not damage the original performance of the thermoplastic resin, the upper limit of the content ratio of the graft copolymer (A) contained in the resin composition is preferably 50% by mass or less, more preferably 45% by mass or less, and further preferably 40% by mass or less, relative to the total mass 100% by mass of the above-mentioned resin composition.

[0288] The above-mentioned preferred upper limit and preferred lower limit can be combined arbitrarily.For example, the content ratio of the graft copolymer (A) included in the resin composition is relative to the gross mass 100 mass % of the above-mentioned resin composition, preferably 1 mass % or more and 50 mass % or less, more preferably 10 mass % or more and 45 mass % or less, further preferably 20 mass % or more and 40 mass % or less.

[0289] From the viewpoint that the obtained molded article does not damage the original performance of the thermoplastic resin, the lower limit of the content ratio of the thermoplastic resin (B) contained in the resin composition in the third embodiment of the present invention is preferably 50% by mass or more, more preferably 55% by mass or more, and further preferably 60% by mass or more relative to the total mass 100% by mass of the above-mentioned resin composition. On the other hand, from the viewpoint that the obtained molded article has excellent impact resistance, the upper limit of the content ratio of the thermoplastic resin (B) contained in the resin composition is preferably 99% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less relative to the total mass 100% by mass of the above-mentioned resin composition.

[0290] The above-mentioned preferred upper limit and preferred lower limit can be combined arbitrarily.For example, the content ratio of the thermoplastic resin (B) included in the resin composition is preferably 50% by mass or more and 99% by mass or less relative to the gross mass 100% by mass of the above-mentioned resin composition, more preferably 55% by mass or more and 90% by mass or less, and further preferably 60% by mass or more and 80% by mass or less.

[0291] From the viewpoint of excellent scratch resistance, product processability and impact resistance of the obtained molded article, the lower limit of the ratio of the fatty acid compound (C) included in the resin composition in the 3rd embodiment of the present invention is relative to the gross mass 100 mass % of the above-mentioned resin composition, preferably more than 0.01 mass %, more preferably more than 0.1 mass %, more preferably more than 1.0 mass %. On the other hand, from the viewpoint of maintaining the product processability and impact resistance of the obtained molded article well, not damaging the original performance of thermoplastic resin (B), the upper limit of the ratio of the fatty acid compound (C) included in the resin composition is relative to the gross mass 100 mass % of the above-mentioned resin composition, preferably less than 10 mass %, more preferably less than 6.0 mass %. It can be less than 3.0 mass %.

[0292] The above-mentioned preferred upper limit and preferred lower limit can be combined arbitrarily.For example, the containing ratio of the fatty acid compound (C) comprised by resin combination is relative to the gross mass 100 mass % of the above-mentioned resin combination, preferably 0.01 mass % or more and 10 mass % or less, more preferably 0.1 mass % or more and 6.0 mass % or less.Can be 1.0 mass % or more and 3.0 mass % or less.

[0293] The resin composition in the third embodiment of the present invention may further contain other thermoplastic resins such as polystyrene (GPPS), high impact polystyrene (HIPS), ABS, SAN, AS, and MS resins, polyphenylene ether resins, polycarbonate resins, polyester resins, polyacetal resins, polyvinyl chloride resins, polyethylene, polypropylene, and other polyolefin resins, within a range that does not impair the effects of the third embodiment of the present invention.

[0294] The resin composition in the third embodiment of the present invention may contain the other thermoplastic resin in an amount of 10% by mass or less relative to 100% by mass of the total mass of the resin composition, preferably 5% by mass or less. Alternatively, the resin composition in the third embodiment of the present invention may not contain the other thermoplastic resin.

[0295] The lower limit of the gel content of the resin composition in the third embodiment of the present invention is not particularly limited, but is 1% by mass or more from the viewpoint of excellent impact resistance of the obtained molded article. It is more preferably 5% by mass or more, and further preferably 10% by mass or more. On the other hand, from the viewpoint of excellent product processability of the obtained molded article, the upper limit of the gel content of the resin composition is 35% by mass or less. It is more preferably 30% by mass or less, and further preferably 25% by mass or less.

[0296] For example, the gel content of the resin composition of the present invention is preferably 1% by mass to 35% by mass, more preferably 5% by mass to 30% by mass, and further preferably 10% by mass to 25% by mass.

[0297] In addition, the specific measurement method of the gel content of the resin composition will be described later.

[0298] The lower limit of the tensile elongation of the resin composition in the third embodiment of the present invention is preferably 20% or more, more preferably 25% or more. The tensile elongation becomes an indicator related to the processability of the product when manufacturing a molded product comprising the resin composition in the third embodiment of the present invention and applying it to various uses. The greater the tensile elongation, the better the processability of the product. There is no particular limit to the upper limit of the tensile elongation. If it is 60% or less, the residual stress of the resulting molded product can be reduced. In addition, during the transportation of the product in the manufacturing process and during the manufacturing and collection, the product is not prone to slack and wrinkles. As a method for making the tensile elongation 20% or more, there is no particular limitation, and for example, the composition of the resin composition is the above-mentioned preferred type, combination, and compounding amount.

[0299] In addition, the specific measuring method of tensile elongation will be described later.

[0300] <Graft copolymer (A)>

[0301] The graft copolymer (A) is one of the constituent components of the resin composition in the third embodiment of the present invention.

[0302] The graft copolymer (A) is a graft copolymer obtained by graft-polymerizing a monomer containing a (meth)acrylate compound described later and a composite rubber (c) composed of a polyorganosiloxane (a) and an alkyl acrylate rubber (b) described later.

[0303] The graft copolymer (A) can be used as a graft copolymer obtained by grafting and polymerizing 30 to 70 parts by mass of a monomer containing a (meth)acrylate compound and 30 to 70 parts by mass of a composite rubber (c) with 100 parts by mass of the graft copolymer (A). If the content of the composite rubber (c) is 30 parts by mass or more, the impact resistance of the molded article becomes good. The lower limit of the content of the composite rubber (c) is more preferably 35 parts by mass or more, and more preferably 40 parts by mass or more. In addition, if the content of the composite rubber (c) is 70 parts by mass or less, the color development and appearance of the molded article become good. The upper limit of the content of the composite rubber (c) is more preferably 65 parts by mass or less, and more preferably 60 parts by mass or less.

[0304] Taking the graft copolymer (A) as 100 parts by mass, the monomer containing the (meth) acrylate compound grafted with the composite rubber (c) can be set to 30 parts by mass or more and 70 parts by mass or less. If the monomer containing the (meth) acrylate compound is 30 parts by mass or more, the color development and appearance become good. If the monomer containing the (meth) acrylate compound is 70 parts by mass or less, the impact resistance of the molded article becomes good. The lower limit of the amount of the monomer containing the (meth) acrylate compound is more preferably 35 parts by mass or more, and more preferably 40 parts by mass or more. The upper limit of the amount of the monomer containing the (meth) acrylate compound is more preferably 65 parts by mass or less, and more preferably 60 parts by mass or less.

[0305] <Compound rubber (c)>

[0306] The composite rubber (c) is one of the constituent components of the resin composition in the third embodiment of the present invention.

[0307] The composite rubber (c) is a composite rubber comprising the polyorganosiloxane (a) and the alkyl acrylate rubber (b), and more specifically, is a polymer obtained by polymerizing a monomer mixture comprising an acrylate monomer (hereinafter abbreviated as “acrylate monomer mixture”) and the polyorganosiloxane (a).

[0308] As the polyorganosiloxane, polydimethylsiloxane is preferred from the viewpoint of improving the impact resistance of the molded article, and the polyorganosiloxane may contain a siloxane containing a vinyl polymerizable functional group and a siloxane-based crosslinking agent having three or more siloxane bonds.

[0309] Relative to the total mass 100 mass % of the above-mentioned polyorganosiloxane and the above-mentioned acrylate monomer mixture, the proportion of the polyorganosiloxane can be set to 1 mass % or more and 20 mass % or less. If the proportion of the polyorganosiloxane is 1 mass % or more, the impact resistance of the molded article becomes good. In addition, if the proportion of the polyorganosiloxane is 20 mass % or less, the color development and appearance of the molded article can be well maintained. The lower limit of the proportion of the polyorganosiloxane is more preferably 2 mass % or more, and more preferably 5 mass % or more. The upper limit of the proportion of the polyorganosiloxane is more preferably 15 mass % or less.

[0310] Examples of the acrylic acid ester monomer include methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate. In view of improving the impact resistance of the resulting molded article, n-butyl acrylate is particularly preferred.

[0311] From the viewpoint that the impact resistance of the molded article becomes good, the above-mentioned acrylate monomer mixture preferably contains 80% by mass or more of acrylate monomer relative to the total mass 100% by mass of the acrylate monomer mixture. If the acrylate monomer is more than 80% by mass, the color development and appearance of the molded article become good. The lower limit of the acrylate monomer is more preferably more than 85% by mass, and more preferably more than 90% by mass. In the above-mentioned acrylate monomer mixture, relative to the total mass 100% by mass of the monomer mixture, other vinyl monomers that can be copolymerized with the acrylate monomer can be included in an amount of less than 20% by mass. If other vinyl monomers are less than 20% by mass, the color development and appearance of the molded article become good. The lower limit of other vinyl monomers is more preferably less than 15% by mass, and more preferably more than 10% by mass.

[0312] Relative to the total mass 100 mass % of the above-mentioned polyorganosiloxane and the above-mentioned acrylate monomer mixture, the ratio of the acrylate monomer mixture relative to the total mass 100 mass % of the composite rubber (c) can be set to 80 mass % or more and 99 mass % or less. If the ratio of the acrylate monomer mixture is more than 80 mass %, the color development and appearance of the molded product become good. If the ratio of the acrylate monomer mixture is less than 99 mass %, the impact resistance of the molded product can be well maintained. The lower limit of the ratio of the acrylate monomer mixture is more preferably more than 85 mass %. The upper limit of the ratio of the acrylate monomer mixture is more preferably less than 98 mass %, and further preferably less than 95 mass %.

[0313] The mass average particle size of the composite rubber (c) is preferably 0.07um or more and 0.15um or less. If the mass average particle size of the composite rubber (c) is more than 0.07um, the impact resistance of the molded product becomes good. If the mass average particle size of the composite rubber (c) is less than 0.15um, the color development and appearance of the molded product become good. In addition, the lower limit of the mass average particle size of the composite rubber (c) is more preferably more than 0.09um, and the upper limit is more preferably less than 0.13um. The adjustment of the mass average particle size can use a known method.

[0314] As the monomer containing a (meth)acrylate compound grafted to the composite rubber (c), methacrylate, acrylate, etc. are preferred. Examples of methacrylate include methyl methacrylate, ethyl methacrylate, 2-ethylhexyl methacrylate, etc. Examples of acrylate include methyl acrylate, ethyl acrylate, n-butyl acrylate, etc. Among these, a mixture of methacrylate and acrylate is preferred, and a mixture of methyl methacrylate and methyl acrylate, or a mixture of methyl methacrylate and ethyl acrylate is particularly preferred from the perspective of excellent weather resistance, color development, appearance, and thermal stability.

[0315] The monomer containing a (meth)acrylate compound grafted to the composite rubber (c) preferably contains 80% by mass or more of the (meth)acrylate compound relative to 100% by mass of the total mass of the monomer. If the (meth)acrylate compound is 80% by mass or more, weather resistance, color development, appearance, and thermal stability become good. More preferably, the monomer containing a (meth)acrylate compound contains 80% by mass or more of methacrylate.

[0316] The monomer containing (meth)acrylate compound grafted with the composite rubber (c) can contain other vinyl monomers that can copolymerize with the (meth)acrylate compound. As other vinyl monomers that can copolymerize with the (meth)acrylate compound, aromatic vinyl monomers such as styrene-α-methylstyrene, cyanide vinyl monomers such as acrylonitrile-methacrylonitrile, cyclic vinyl monomers such as maleic anhydride-N-substituted maleimide, etc. can be cited. The other vinyl monomers that can copolymerize with the (meth)acrylate compound are preferably less than 20% by mass relative to the total mass 100% by mass of the monomer. If the other vinyl monomers are less than 20% by mass, the weather resistance, color development, appearance, and thermal stability of the resulting molded product become good.

[0317] The graft copolymer (A) can be produced by a known polymerization method, and among these, production by emulsion polymerization is particularly preferred from the viewpoint of easy control of particle size and easy control of core-shell structure.

[0318] The lower limit of the gel content of the graft copolymer (A) is not particularly limited, but is 40% by mass or more from the viewpoint of excellent impact resistance of the obtained molded article. It is more preferably 50% by mass or more, and further preferably 55% by mass or more. On the other hand, the upper limit of the gel content of the graft copolymer (A) is 99% by mass or less from the viewpoint of excellent product processability of the obtained molded article. It is more preferably 95% by mass or less, and further preferably 90% by mass or less.

[0319] The above-mentioned preferred upper limit and preferred lower limit can be arbitrarily combined. For example, the gel content of the graft copolymer (A) in the third embodiment of the present invention is preferably 40% by mass or more and 99% by mass or less, more preferably 50% by mass or more and 95% by mass or less, and further preferably 55% by mass or more and 90% by mass or less.

[0320] Here, the gel content of the graft copolymer (A) can be calculated by the following formula.

[0321] G'=(m' / M')×100

[0322] In the formula, G' (%) represents the gel content of the graft copolymer (A), M' represents the mass of a predetermined amount of the graft copolymer (A) (also referred to as the mass before extraction), and m' represents the mass of the acetone-insoluble matter of the predetermined amount of the graft copolymer (A) (also referred to as the mass after extraction).

[0323] Since the gel content of the resin composition is 35% by mass or less, when the gel content of the graft copolymer (A) is 80% by mass or more, the gel content of the resin composition can be adjusted by further containing a thermoplastic resin (B). The ratio of the content of the graft copolymer (A) to the thermoplastic resin (B) in the resin composition can be appropriately set so that the gel content of the resin composition becomes a desired value.

[0324] <Thermoplastic resin (B)>

[0325] The thermoplastic resin (B) is one of the constituent components of the resin composition in the third embodiment of the present invention.

[0326] Examples of the thermoplastic resin (B) include olefin resins such as polypropylene and polyethylene; styrene resins such as polystyrene, (meth)acrylate-styrene copolymers, styrene-acrylonitrile copolymers, and styrene-maleic anhydride copolymers; acrylic resins such as polymethyl methacrylate; polycarbonate resins; polyamide resins; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polylactic acid; engineering plastics such as (modified) polyphenylene ether resins, polyoxymethylene resins, polysulfone resins, polyarylate resins, and polyphenylene resins; vinyl chloride resins such as rigid vinyl chloride resins, semirigid vinyl chloride resins, and soft vinyl chloride resins, etc. These thermoplastic resins (B) can be used alone or in combination of two or more.

[0327] Among these, acrylic resins are preferred because the resulting molded article has excellent weather resistance, color development, appearance, and the like.

[0328] Specifically, the acrylic resin is preferably a (meth)acrylate polymer containing a repeating unit derived from a (meth)acrylate monomer.

[0329] When the thermoplastic resin (B) contains a (meth)acrylate polymer, the weather resistance, color development property, and appearance of the obtained molded article become good.

[0330] Specifically, the (meth)acrylate polymer is preferably a polymer containing 80% by mass or more of a repeating unit derived from a (meth)acrylate monomer relative to 100% by mass of the total mass of the (meth)acrylate polymer.

[0331] Specifically, as the (meth)acrylate-based polymer, a copolymer containing a repeating unit derived from methacrylate and a repeating unit derived from acrylate is more preferred.

[0332] The methacrylate and acrylate that can be used are the same methacrylate and acrylate as those used in the graft copolymer (A), and among them, a copolymer of methyl methacrylate and methyl acrylate is particularly preferred.

[0333] The (meth)acrylate polymer may contain components other than methacrylate and acrylate as necessary.

[0334] Examples of other components include aromatic vinyl monomers such as styrene-α-methylstyrene, cyanide vinyl monomers such as acrylonitrile-methacrylonitrile, and cyclic vinyl monomers such as maleic anhydride-N-substituted maleimide.

[0335] By using these other components, desired properties such as moldability, appearance, color development, impact strength, and heat resistance of the obtained molded article can be improved.

[0336] The thermoplastic resin (B) preferably contains 80% by mass or more of a (meth)acrylate monomer component. If the (meth)acrylate monomer component is 80% by mass or more, the weather resistance, color development, appearance, etc. of the resulting molded product become good. The content ratio of the (meth)acrylate monomer component is more preferably 90% by mass or more, and further preferably 95% by mass or more.

[0337] <Fatty acid compound (C)>

[0338] The fatty acid compound (C) is one of the constituent components of the resin composition in the third embodiment of the present invention.

[0339] The resin composition according to the third embodiment of the present invention is characterized in that a fatty acid compound (C) and a graft copolymer (A) containing a silicone-based component are used together.

[0340] In the past, it was known that fatty acid compounds (C) improve the scratch resistance of resin molded products, but the effect of improving the impact resistance of resin molded products was not known. However, in the present invention, when the fatty acid compound (C) is used in combination with a graft copolymer (A) containing an organosilicon component, the impact resistance of the obtained molded product is found to be better than when the graft copolymer (A) containing no organosilicon component is used in combination. Furthermore, it is also found that the product processability or scratch resistance of the obtained molded product is also better.

[0341] The fatty acid compound (C) is preferably a chain hydrocarbon compound having at least one carbonyl group or carboxyl group in the molecule, from the viewpoint of easily making the obtained molded article excellent in scratch resistance.

[0342] The so-called chain hydrocarbon compound having at least one carbonyl group or carboxyl group in the molecule refers to a compound in which the carbon atom to which the carbonyl group or carboxyl group is bonded becomes a constituent atom of the carbon chain. The carbon chain in the chain hydrocarbon compound having at least one carbonyl group or carboxyl group in the molecule may be saturated or unsaturated, and may be straight chain or branched.

[0343] As such fatty acid compound (C), for example, as a chain hydrocarbon compound having a carboxyl group in the molecule, fatty acids and their derivatives can be cited. As a chain hydrocarbon compound having an amide group in the molecule, fatty acid amides and their derivatives can be cited. As a chain hydrocarbon compound having an ester group or a carbonyl group in the molecule, fatty acid alkyl esters and their derivatives, or fatty acid glycerides and their derivatives can be cited.

[0344] Derivatives of fatty acids, derivatives of fatty acid amides, derivatives of fatty acid alkyl esters, and derivatives of fatty acid glycerides are compounds having structures in which hydrogen atoms in chain hydrocarbon compounds or part or all of side chains are replaced with other organic groups. Examples of the organic group include polyether groups, polyalkyl groups, aralkyl groups, and polyester groups, which may be singular or in combination of two or more.

[0345] Furthermore, as the derivative of the fatty acid amide, it is possible to appropriately select and use it from various compounds such as monoamide and bisamide according to various situations.

[0346] These fatty acid compounds (C) may be used alone or in combination of two or more.

[0347] The lower limit of the melting point of the fatty acid compound (C) is not particularly limited, but is preferably 90°C or higher from the viewpoint that the scratch resistance of the obtained molded article becomes better. The reason for this is not clear, but it is speculated that this is because if the melting point is above 90°C, the fatty acid compound (C) contained in the methacrylic resin composition volatilizes in the mold during injection molding, adheres to the mold surface and is easily liquefied and condensed, and the amount of the fatty acid compound (C) discharged from the gas outlet in the form of gas is reduced and suppressed, resulting in a tendency that the fatty acid compound (C) can exist at a high content ratio on the surface and near the surface of the obtained molded article. The melting point of the fatty acid compound (C) is more preferably above 95°C, and further preferably above 100°C. On the other hand, the upper limit of the melting point of the fatty acid compound (C) is not particularly limited, but is preferably below 150°C from the viewpoint that the scratch resistance of the obtained molded article becomes better. The reason is not clear, but it is presumed that this is because if the melting point of the fatty acid compound (C) is 150°C or less, the fatty acid compound (C) contained in the methacrylic resin composition can be fully volatilized in the mold during injection molding, and the above-mentioned action and effect can be easily obtained. The melting point of the fatty acid compound (C) is more preferably 130°C or less, and further preferably 120°C or less.

[0348] The upper and lower limits of the melting point of the fatty acid compound (C) can be arbitrarily combined. For example, the melting point of the fatty acid compound (C) is preferably 90°C to 150°C, more preferably 95°C to 130°C, and even more preferably 100°C to 120°C.

[0349] The upper limit of the 10% weight reduction temperature of the fatty acid compound (C) is not particularly limited, but is preferably 350°C or lower from the viewpoint of improving the scratch resistance of the obtained molded article. The reason for this is not clear, but it is speculated that this is because the fatty acid compound (C) contained in the methacrylic resin composition is volatilized in the mold during injection molding. The lower the 10% weight reduction temperature, the easier it is for the fatty acid contained in the methacrylic resin composition to volatilize in the mold during injection molding. As a result, in the methacrylic resin composition injected into the mold later, the fatty acid compound (C) attached to the mold surface and liquefied or condensed diffuses and moves, so that the fatty acid compound (C) is finally present at a high content ratio on the surface and near the surface of the obtained molded article. The 10% weight reduction temperature of the fatty acid compound (C) is more preferably 300°C or lower, and further preferably 260°C or lower.

[0350] On the other hand, the lower limit of the 10% weight loss temperature of the fatty acid compound (C) is not particularly limited, but is preferably 190°C or higher from the viewpoint of improving the scratch resistance of the obtained molded article. The reason for this is not clear, but it is presumed that this is because if the 10% weight loss temperature is 190°C or higher, the fatty acid compound (C) will not be thermally decomposed during injection molding, and the effect of the fatty acid compound (C) can be fully demonstrated. The 10% weight loss temperature of the fatty acid compound (C) is more preferably 200°C or higher, and further preferably 210°C or higher.

[0351] The upper limit and lower limit of the 10% weight loss temperature of the fatty acid compound (C) can be arbitrarily combined. For example, the 10% weight loss temperature of the fatty acid compound (C) is preferably 190°C to 350°C, more preferably 200°C to 300°C, and further preferably 210°C to 260°C.

[0352] Among these fatty acid compounds (C), fatty acid amide compounds and derivatives thereof (hereinafter, these are also collectively referred to as "fatty acid amide compounds (C1)").

[0353] As the fatty acid amide compound (C1), a compound represented by the following general formula (i) (hereinafter also referred to as "compound (i)") can be used. Compound (i) is preferred because even a small amount thereof can provide a molded article with excellent scratch resistance and is unlikely to impair the original performance of the thermoplastic resin.

[0354] R-CONH2(i)

[0355] (In the general formula (i), R is a hydrocarbon group having 10 to 25 carbon atoms which may have a substituent.)

[0356] From the viewpoint of excellent compatibility with the (meth)acrylic polymer (B1) and excellent scratch resistance of the obtained molded article, the lower limit of the number of carbon atoms of R in the formula (i) of the fatty acid amide compound (C1) is preferably 10 or more, more preferably 15 or more, and even more preferably 17 or more. From the viewpoint of good dispersibility of the fatty acid compound (C) in the methacrylic resin composition and good scratch resistance of the obtained molded article, the upper limit of the number of carbon atoms of R in the formula (i) of the fatty acid amide compound (C1) is preferably 25 or less, more preferably 24 or less, and even more preferably 23 or less.

[0357] The above-mentioned preferred upper limit and preferred lower limit can be arbitrarily combined. For example, the number of carbon atoms of R in the formula (i) of the fatty acid amide compound is preferably 10-25, more preferably 15-24, and even more preferably 17-23.

[0358] Among the fatty acid compounds (C), the fatty acid amide compound (C1) is preferred from the viewpoint of excellent compatibility with the (meth)acrylic polymer (B1), fluidity of the methacrylic resin composition, and scratch resistance of the obtained molded article.

[0359] Examples of the fatty acid amide compound (C1) include saturated fatty acid amide compounds, unsaturated fatty acid amide compounds, bisfatty acid amide compounds, and hydroxymethyl fatty acid amide compounds. These fatty acid amide compounds may be used alone or in combination of two or more.

[0360] Examples of the saturated fatty acid amide compound include lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, and hydroxymethylstearic acid amide. These saturated fatty acid amide compounds may be used alone or in combination of two or more.

[0361] Examples of the unsaturated fatty acid amide include erucic acid amide, oleic acid amide, brassinoic acid amide, and elaidic acid amide. These unsaturated fatty acid amide compounds may be used alone or in combination of two or more.

[0362] Among these unsaturated fatty acid amide compounds, erucic acid amide and oleic acid amide are preferred, and erucic acid amide is more preferred, since the obtained molded article has excellent scratch resistance.

[0363] Examples of the bis fatty acid amide compound include bis fatty acid amides such as methylene bis stearic acid amide, methylene bis oleic acid amide, ethylene bis stearic acid amide, and ethylene bis oleic acid amide; stearyl stearic acid amide, stearyl erucic acid amide, and oleyl palmitamide. These bis fatty acid amide compounds may be used alone or in combination of two or more.

[0364] Among the fatty acid amide compounds (C1), saturated fatty acid amide compounds are preferred because the obtained molded article has more excellent scratch resistance.

[0365] From the perspective of obtaining a molded article with further excellent scratch resistance, it is more preferred that the saturated fatty acid amide compound contains either stearic acid amide or palmitic acid amide, and it is further preferred that the saturated fatty acid amide compound contains stearic acid amide and palmitic acid amide as main components. Here, the so-called "containing as main components" means that the total mass of stearic acid amide and palmitic acid amide is 85.0 mass % or more relative to the total mass 100 mass % of the fatty acid amide compound.

[0366] <Other additives>

[0367] The resin composition in the third embodiment of the present invention may contain other additives in addition to the graft copolymer (A) and the fatty acid compound (C). Other additives include, for example, pigments, stabilizers, reinforcing agents, fillers, flame retardants, foaming agents, lubricants, plasticizers, antistatic agents, etc. These other additives may be used alone or in combination of two or more.

[0368] <Method for producing resin composition>

[0369] The resin composition in the 3rd embodiment of the present invention, for example, can be mixed with a predetermined amount of a graft copolymer (A), a thermoplastic resin (B) and a fatty acid compound (C), and after the mixture is melt-mixed using a known melt-mixing means, the resulting melt-mixed product is obtained using a known cutting and crushing device such as a granulator, for example, in the form of particles. As a known melt-mixing means, a single-screw extruder, a double-screw extruder, a Banbury mixer, a pressure kneading machine, a roller, etc. can be used. Alternatively, the above-mentioned mixture can also be used as the manufacturing raw material of a direct molded product.

[0370] <Molding products>

[0371] The molded article in the third embodiment of the present invention is obtained by molding the resin composition in the third embodiment of the present invention.

[0372] As a method for obtaining a molded product, for example, injection molding, extrusion molding, pressure molding, blow molding, compression molding, calendar molding, inflation molding and other known molding methods can be cited. In addition, the obtained molded product can be further subjected to secondary molding using known molding methods such as air pressure molding and vacuum molding. Molding conditions such as molding temperature and molding pressure can be appropriately set.

[0373] From the perspective of excellent scratch resistance, impact resistance and product processability, the resin composition and molded product in the third embodiment of the present invention can be preferably used for various molded products such as exterior and interior material parts for vehicles, wall materials, building material parts such as window frames, tableware, toys, home appliance parts, interior components, etc.

[0374] Example

[0375] Hereinafter, the present invention will be specifically described by way of Examples and Comparative Examples. However, the present invention is not limited to these Examples.

[0376] In addition, in the present examples, "parts" and "%" mean "parts by mass" and "mass %" unless otherwise specified.

[0377] Various measurements and evaluations in Examples and Comparative Examples were performed by the following methods.

[0378] [Measurement and evaluation methods]

[0379] (1) Preparation of test pieces for evaluation

[0380] <Production of molded product X1A>

[0381] The resin composition obtained from the examples and comparative examples was dried with hot air at 80°C for about 4 hours, and then injection molded using an injection molding machine (machine type name: EC75SXIII-2A, manufactured by Toshiba Machine Co., Ltd.) at a molding temperature of 210°C and a mold temperature of 40°C to obtain a test piece of a molded product X1A with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm.

[0382] <Production of molded product X2A>

[0383] The resin composition obtained from the examples and comparative examples was dried with hot air at 80°C for about 4 hours, and then injection molded using an injection molding machine (machine type name: EC20PN-II, manufactured by Toshiba Machine Co., Ltd.) at a molding temperature of 210°C and a mold temperature of 40°C to obtain a test piece of a molded product X2A with a length of 50 mm, a width of 50 mm, and a thickness of 3 mm.

[0384] (2) Evaluation of heat resistance

[0385] The molded product X1A was measured for load deflection temperature (HDT) (° C.) at a load of 0.45 MPa using a HDT / VICAT tester (machine model name: "No. 148-HD-PC3 Heat Deformation Tester", manufactured by Yasuda Seiki Co., Ltd.) in accordance with ISO75-1.2.

[0386] In addition, before the measurement, the test piece was annealed at a temperature of 50° C. for 16 hours.

[0387] The case where the HDT was 65°C or higher was judged as "A", the case where the HDT was 61.5 or higher and less than 65 was judged as "B", and the case where the HDT was 9.2 or higher and less than 61.5 was judged as "C". The higher the HDT, the better the heat resistance.

[0388] (3) Evaluation of impact resistance

[0389] The molded product X1A was tested for notched Charpy impact strength (kJ / m2) at 23°C using a digital impact tester (machine model name: DG-UB, manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ISO 179-1. 2 ).

[0390] The case where the Charpy impact strength is 20 or more is judged as "A", the case where the Charpy impact strength is 10.5 or more and less than 20 is judged as "B", the case where the Charpy impact strength is 9.2 or more and less than 19.5 is judged as "C", and the case where the Charpy impact strength is less than 9.2 is judged as "D". The larger the Charpy impact strength, the better the impact resistance.

[0391] (4) Evaluation of transparency

[0392] The molded article X2A was measured for total light transmittance (%) in accordance with ISO 13468 using a haze meter (model name: NDH4000, manufactured by Nippon Denshoku Industries, Ltd.), and for haze value (%) in accordance with ISO 14782.

[0393] The case where the total light transmittance is 70 or more is judged as "A", the case where the total light transmittance is 63.5 or more and less than 70 is judged as "B", the case where the total light transmittance is 61 or more and less than 63.5 is judged as "C", and the case where the Charpy impact strength is less than 61 is judged as "D". The larger the total light transmittance, the better the transparency.

[0394] A haze value of 40 or less was determined as "A", a haze value of more than 40 and 55 or less was determined as "B", and a haze value of more than 55 was determined as "C". The smaller the haze value, the better the transparency.

[0395] (5) Evaluation of bending mechanical properties

[0396] The molded article X1A was subjected to a three-point bending test using a tensile testing machine (machine model name: STROGRAPH TF, manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ISO 178 to measure the flexural modulus (MPa) and flexural stress (MPa).

[0397] In addition, before the measurement, the test piece was annealed at a temperature of 50° C. for 16 hours.

[0398] The case where the bending stress (MPa) was 58 or less was judged as "A", the case where the bending stress exceeded 58 and was 65 or less was judged as "B", and the case where the bending modulus exceeded 65 was judged as "C".

[0399] The case where the bending modulus (MPa) was 1.85 or less was judged as "A", the case where the bending modulus was more than 1.85 and 2.21 or less was judged as "B", and the case where the bending modulus was more than 2.21 was judged as "C".

[0400] (6) Measurement of Refractive Index and Total Refractive Index Rab of Polylactic Acid Polymer (D) and (Meth) Acrylic Acid Polymer (B1)

[0401] A resin composition molded body made of only a polylactic acid polymer (D) and an acrylic resin (B1) was used to prepare a film with a thickness of about 1 mm by hot pressing (190°C, preheated for 3 minutes, pressed for 5 minutes, and then cooled for 2 minutes). The obtained film was measured by an Abbe refractometer in accordance with ASTM-D542. A saturated aqueous solution of zinc chloride was used as the contact liquid. ·Determination of the refractive index Rc of the graft copolymer (A) A film with a thickness of about 1 mm was prepared from the powder of the graft copolymer (A) by hot pressing (150°C, preheated for 5 minutes, pressed for 1 minute, and then cooled for 2 minutes). The refractive index of the film was measured by an Abbe refractometer in accordance with ASTM-D542. A saturated aqueous solution of zinc chloride was used as the contact liquid.

[0402] (Material)

[0403] Polylactic acid polymer (D-1): Ingeo 2500HP (product name, manufactured by Nature Works)

[0404] Acrylic resin (B-1): ACRYPET VH 001 (trade name, manufactured by Mitsubishi Chemical Corporation, an acrylic resin containing 95% by mass or more of repeating units derived from methyl methacrylate)

[0405] Graft copolymer (A-1): METABLEN W600A (trade name, manufactured by Mitsubishi Chemical Corporation, an acrylic rubber graft copolymer obtained by graft-polymerizing a vinyl monomer and an acrylic rubber)

[0406] Graft copolymer (A-2): METABLEN S2260 (trade name, manufactured by Mitsubishi Chemical Corporation, a polyorganosiloxane-acrylic rubber graft copolymer obtained by graft-polymerizing a vinyl monomer with a polyorganosiloxane-acrylic rubber)

[0407] Graft copolymer (A-3): METABLEN C-950 (trade name, manufactured by Mitsubishi Chemical Corporation, a diene rubber graft copolymer obtained by graft-polymerizing a vinyl monomer and a diene rubber)

[0408] Fatty acid compound (C-1): a mixture of fatty acid amides containing stearic acid amide and palmitic acid amide as main components (trade name: Fatty acid amide S, manufactured by Kao Corporation)

[0409] [Example 1A]

[0410] After manually blending the materials in the ratios shown in Table 1A, the materials were kneaded using a twin-screw extruder (machine type name "PCM30", L / D = 25, manufactured by Ikegai Co., Ltd.) at a barrel temperature of 210°C, a die temperature of 210°C, and a screw speed of 250 rpm to obtain a pelletized thermoplastic resin composition. The evaluation results of the obtained thermoplastic resin composition are shown in Table 1A.

[0411] [Examples 2A to 14A, Comparative Examples 1A to 3A]

[0412] A pelletized thermoplastic resin composition was obtained in the same manner as in Example 1A except that the types or ratios of the materials were changed to the formulations shown in Table 1A. The evaluation results of the obtained thermoplastic resin composition are shown in Table 1A.

[0413] [Table 1A]

[0414]

[0415] From the results of the present examples and comparative examples, it is understood that the molded article obtained from the resin composition in the second embodiment of the present invention is excellent in transparency, impact resistance, heat resistance, and mechanical properties such as flexural modulus and flexural stress.

[0416] Since the thermoplastic resin composition of Comparative Example 1A does not contain the polylactic acid-based polymer (D), it is inferior in impact resistance and transparency.

[0417] In the thermoplastic resin composition of Comparative Example 2A, since the content of the graft copolymer (A) was small, the impact resistance, flexural mechanical properties (flexural stress), and transparency (haze) were poor.

[0418] In the thermoplastic resin composition of Comparative Example 3A, since the content of the graft copolymer (A) was small, the flexural mechanical properties (flexural stress, flexural modulus) were inferior.

[0419] <Evaluation Method>

[0420] Evaluations in Examples and Comparative Examples were performed by the following methods.

[0421] (1) Preparation of test pieces for evaluation

[0422] <Production of molded product X1B>

[0423] After the resin composition obtained from the examples and comparative examples was dried at 80°C for about 12 hours, it was injection molded using an injection molding machine (machine type name: EC75SXIII-2A, manufactured by Toshiba Machine Co., Ltd.) at a molding temperature of 250°C and a mold temperature of 60°C to obtain a test piece (molded product X1B) having a length of 80 mm, a width of 10 mm, and a thickness of 4 mm.

[0424] <Production of molded product X2B>

[0425] The resin composition obtained from the examples and comparative examples was dried at 80°C for about 12 hours, and then injection molded using an injection molding machine (machine type name: EC75SXIII-2A, manufactured by Toshiba Machine Co., Ltd.) at a molding temperature of 210°C and a mold temperature of 40°C to obtain a test piece (molded product X2B) having a length of 100 mm, a width of 100 mm, and a thickness of 3 mm.

[0426] <Production of molded product X3B>

[0427] After the resin composition obtained from the examples and comparative examples was dried at 80°C for about 12 hours, it was injection molded using an injection molding machine (machine type name: EC75SXIII-2A, manufactured by Toshiba Machine Co., Ltd.) at a molding temperature of 230°C and a mold temperature of 60°C to obtain a dumbbell test piece (molded product X3B) having a length of 150 mm, a width of 10 mm, and a thickness of 4 mm.

[0428] (2) Evaluation of impact resistance

[0429] As an index of impact resistance, the notched Charpy impact strength (kJ / m2) of the molded product X1B was measured at a temperature of 23°C in accordance with ISO 179-1 using a digital impact tester (machine model name: DG-UB, manufactured by Toyo Seiki Seisaku-sho, Ltd.). 2 ).

[0430] The case where the Charpy impact strength is 8.0 or more is judged as "A", the case where the Charpy impact strength is 3.0 or more and less than 8.0 is judged as "B", and the case where the Charpy impact strength is less than 3.0 is judged as "C". The larger the Charpy impact strength, the better the impact resistance.

[0431] (3) Evaluation of product processability

[0432] As an index of product processability, the molded product X3B was subjected to a tensile test using a tensile testing machine (machine type name: STROGRAPHT-F, manufactured by Toyo Seiki Seisaku-sho) in accordance with JIS K6723 at a tensile speed of 50 mm / min to measure the tensile elongation (%). The higher the tensile elongation, the better the product processability of the resin composition becomes.

[0433] In addition, before the measurement, the test piece was annealed at a temperature of 50° C. for 16 hours.

[0434] The tensile elongation (%) was judged as "AA" when it was 25% or more, "A" when it was 20% or more and less than 25%, "B" when it was 15% or more and less than 20%, and "C" when it was less than 15%.

[0435] (4) Evaluation of scratch resistance

[0436] As an index of the color development property of the thermoplastic resin composition, the glossiness of the test piece before and after the scratch resistance test was measured by the following method, and the difference therebetween (glossiness difference) was calculated.

[0437] The molded product X2B was placed on a platform and a steel wool abrasion tester (Positioning Actuators, machine type name: XY-FS0010-902, manufactured by Nippon Seiko Co., Ltd.) was used as a friction element. A friction element was formed by overlapping 5 medical gauze (100% earth TOMBO cotton, manufactured by Yamato Works Co., Ltd.) on a flat friction element (diameter 24 mm). Figure 1 As shown, on the surface of the molded product X2B, from the gate position during injection molding to the MD direction (flow direction during molding), the friction element is moved back and forth 200 times at a distance of 50 mm under a load of 500 g in a manner that allows the central portion 3 of the molded product X2B to pass, thereby forming a friction wear treatment portion 1 on the surface of the molded product X2B.

[0438] Next, regarding the test pieces before and after the scratch resistance test, a mirror gloss meter (machine type name: MULTIGLOSS268Plus, manufactured by KONICA MINOLTA Co., Ltd.) was used to make light incident in a direction parallel to the reciprocating direction of the friction element on the central part 3 of the molded product X2B (the test piece subjected to the scratch resistance test is the central part of the surface formed with the friction wear treatment part 2) so that the incident light beam had a diameter of 15 mm. The 60° gloss was measured in accordance with JJIS Z 8741-1997, and the change in 60° gloss before and after the scratch resistance test (gloss difference) was calculated by the following formula (1B).

[0439] Glossiness difference = glossiness of the test piece after the scratch resistance test - glossiness of the test piece before the scratch resistance test Formula (1B)

[0440] The scratch resistance was determined according to the following criteria.

[0441] AA: The glossiness difference is -1.5 or more.

[0442] A: The glossiness difference is -3.0 or more and less than -1.5.

[0443] B: The glossiness difference is -4.0 or more and less than -3.0.

[0444] C: The gloss difference is less than -4.0.

[0445] (5) Gel content of resin composition

[0446] About 1.0 g of the resin composition obtained from the embodiment and the comparative example is weighed to three decimal places using an electronic balance, and this is defined as the mass before extraction M (unit: g). Next, the above resin composition is dissolved in 100 mL of acetone, and the obtained acetone solution is refluxed at a temperature of 65°C for 4 hours. For the extract of the refluxed acetone solution, a high-speed cooling centrifuge (trade name: CR21G, manufactured by Hitachi Koki Co., Ltd.) is used to centrifuge at a temperature of 4°C and a speed of 14000 rpm for 30 minutes. The extract after the centrifugal separation is removed by decantation to recover the solid of the acetone insoluble matter. The recovered solid is refluxed and centrifuged again under the same conditions as above, and then the solid of the acetone insoluble matter is recovered by decantation. The recovered solid is dried at a temperature of 50°C for 24 hours, and the mass of the solid of the acetone insoluble matter finally obtained is weighed to three decimal places using an electronic balance, and this is defined as the mass after extraction m (unit: g). Next, the gel content G (%) of the resin composition was calculated by the following formula.

[0447] G=(m / M)×100

[0448] (6) Mass Average Particle Size The mass average particle size of the polymer latex was calculated by measuring the absorbance at a wavelength of 700 nm using a UV-visible spectrophotometer (UV-mini1240 manufactured by Shimadzu Corporation) in a solution diluted to a concentration (solid content) of 0.5 g / L of the latex using deionized water, and then calculating the mass average particle size using a conversion formula prepared in advance between the absorbance and the mass average particle size. The conversion formula was calculated using the absorbance and the mass average particle size measured using a transmission electron microscope.

[0449] (Material)

[0450] Graft copolymer (A-1): a polyorganosiloxane-acrylic rubber graft copolymer prepared in Production Example 1, in which a vinyl monomer and a polyorganosiloxane-acrylic rubber are graft polymerized.

[0451] Graft copolymer (A-2): METABLEN C-950 (trade name, manufactured by Mitsubishi Chemical Corporation, a core-shell type diene rubber graft copolymer obtained by graft polymerization of a vinyl monomer and a diene rubber)

[0452] Thermoplastic resin (B-1): ACRYPET VH 001 (trade name, manufactured by Mitsubishi Chemical Corporation, an acrylic resin containing 95% by mass or more of repeating units derived from methyl methacrylate)

[0453] Thermoplastic resin (B-2): ACRYPET VH5 (trade name, manufactured by Mitsubishi Chemical Corporation, an acrylic resin containing 95% by mass or more of repeating units derived from methyl methacrylate)

[0454] Fatty acid compound (C-1): fatty acid amide containing stearic acid amide as a main component (trade name: IncroMax (registered trademark) PS, manufactured by CRODA, 10% weight loss temperature: 246°C, melting point: 109°C)

[0455] Fatty acid compound (C-2): ethylenebisoleamide (trade name: SLIPACKS O, manufactured by Mitsubishi Chemical Corporation, 10% weight loss temperature: 344°C, melting point: 119°C)

[0456] Fatty acid compound (C-3): fatty acid amide containing stearic acid amide as the main component (trade name: fatty acid amide S, manufactured by Kao Corporation, 10% weight loss temperature: 243°C, melting point: 103°C)

[0457] [Manufacturing Example 1] (Manufacturing of polyorganosiloxane latex (L))

[0458] A mixture of 98 parts by mass of octamethylcyclotetrasiloxane, 2 parts by mass of γ-methacryloxypropyldimethoxymethylsilane, 0.67 parts by mass of sodium dodecylbenzenesulfonate and 300 parts by mass of deionized water was stirred at 10,000 rpm for 2 minutes in a homogenizer and then heated at 300 kg / cm 2 The pressure of 10000 g was passed once to obtain a premixed organosiloxane latex.

[0459] In a reactor with a reflux cooler, an aqueous solution consisting of 10 parts by mass of dodecylbenzenesulfonic acid and 90 parts by mass of deionized water was added, and the temperature was raised while stirring until the liquid temperature in the reactor reached 85°C, and then the premixed organosiloxane latex was added dropwise over 4 hours. After the addition was completed, the liquid temperature in the reactor was further maintained for 1 hour, and then cooled until the liquid temperature in the reactor reached near room temperature. Then, the reactants in the reactor were neutralized with a caustic soda aqueous solution to obtain a latex. The solid content concentration of the obtained latex was 17.6% by mass, and the mass average particle size of the polyorganosiloxane in the latex was 0.05 μm.

[0460] (Production of Graft Copolymer (A))

[0461] In a reactor equipped with a reflux cooler, 7 parts by mass of polyorganosiloxane latex (L) (as solid content), 0.2 parts by mass of sodium dodecylbenzenesulfonate, and 200 parts by mass of deionized water (including water in the polyorganosiloxane latex (L)) were added, and then a mixture of 53 parts by mass of n-butyl acrylate, 0.6 parts by mass of allyl methacrylate, 0.2 parts by mass of 1,3-butanediol dimethacrylate, and 0.4 parts by mass of cumene hydroperoxide was added while stirring. After the interior of the reactor was purged with nitrogen, the temperature was raised until the liquid temperature in the reactor reached 50°C, and then an aqueous solution composed of 0.001 parts by mass of ferrous sulfate, 0.003 parts by mass of disodium ethylenediaminetetraacetic acid, 0.3 parts by mass of sodium formaldehyde sulfoxylate, and 2 parts by mass of deionized water was added to carry out polymerization. Due to the heat generated during polymerization, the liquid temperature in the reactor rose to 80°C, and this state was maintained for 1 hour. The mass average particle size of the obtained polyorganosiloxane-acrylate composite rubber was 0.10 μm.

[0462] After the liquid temperature inside the reactor was set to 70° C., a mixed liquid consisting of 36 parts by mass of methyl methacrylate, 4 parts by mass of methyl acrylate, and 0.2 parts by mass of cumene hydroperoxide was added dropwise over 3 hours to carry out polymerization.

[0463] After the dropwise addition of the mixed solution was completed, the mixture was further maintained for 1 hour. Then, the mixture was cooled until the liquid temperature in the reactor reached near room temperature, and a latex of a graft copolymer (A) obtained by graft polymerization of methyl methacrylate and methyl acrylate with a composite rubber composed of polyorganosiloxane and n-butyl acrylate rubber was obtained. The mass average particle size of the graft copolymer in the obtained latex was 0.13 μm.

[0464] In a separately prepared reactor equipped with a reflux cooler, 100 parts of a calcium acetate aqueous solution (3% by mass) was added, and the temperature was raised while stirring until the liquid temperature in the reactor reached 80°C. Next, 100 parts of the latex of the graft copolymer was slowly added dropwise to the calcium acetate to coagulate and obtain a precipitate. Next, the obtained precipitate was separated, washed, dehydrated and then dried to obtain a graft copolymer (A-1).

[0465] [Example 1B]

[0466] The graft copolymer (A-1), thermoplastic resin (B-1) and fatty acid compound (C-1) manufactured by Manufacturing Example 1 were mixed in the proportions shown in Table 1B, and were fully mixed using a Henschel mixer. Then, they were supplied to a twin-screw extruder (machine type name: PCM30, manufactured by Ikegai, φ30 mm, L / D=25), and kneaded under the conditions of barrel temperature of 230°C (setting) and screw speed of 250 rpm to obtain a granular resin composition. The evaluation results of the obtained resin composition are shown in Table 1B. It should be noted that in Table 1B, the content ratios (unit: mass %) of the graft copolymer (A), thermoplastic resin (B) and fatty acid compound (C) in the resin composition are calculated values ​​based on the compounding amount (unit: mass parts) of each component.

[0467] [Examples 2B to 5B, Comparative Examples 1B to 6B]

[0468] A pelletized resin composition was obtained in the same manner as in Example 1B except that the formulation was as shown in Table 1B. The evaluation results of the obtained resin composition are shown in Table 1B.

[0469] [Table 1B]

[0470]

[0471] The molded articles obtained by molding the resin compositions obtained in Examples were excellent in impact resistance, product processability, and scratch resistance.

[0472] On the other hand, the molded article obtained by molding the resin composition obtained in Comparative Example 1B was inferior in molding processability and scratch resistance because the fatty acid compound (C) was not blended.

[0473] The molded article obtained by molding the resin composition obtained in Comparative Example 2B was inferior in impact resistance and molding processability because the graft copolymer (A) was not blended.

[0474] The molded products obtained by molding the resin compositions obtained from Comparative Examples 3B to 6B have poor impact resistance because the graft copolymer does not contain silicone components. In particular, the molded products of Comparative Examples 3B to 5B have poor abrasion resistance. Furthermore, the molded products of Comparative Examples 3B and 4B also have poor molding processability.

[0475] Industrial Availability

[0476] A first aspect of the present invention is to provide a resin composition having excellent mechanical properties and a molded article thereof.

[0477] According to the second embodiment of the present invention, a resin composition and a molded product thereof having excellent mechanical properties of transparency, impact resistance, heat resistance, flexural modulus, and flexural stress of the obtained molded product can be stably provided. Particularly, it is suitable when a sheet or film is subjected to bending molding, blow molding, or vacuum molding.

[0478] Such molded products are suitable for use in optical materials, lighting materials, materials for housing equipment, building materials, and vehicle parts that require these physical properties, as well as in sundries such as toys and stationery, OA equipment, home appliances, and further in packaging, and panels for vending machines, pinball machines, and the like.

[0479] The resin composition in the third embodiment of the present invention is suitable for use as materials for residential equipment such as washbasins, bathtubs, and flush toilets; building materials for outdoor use such as billboards, window frames, or exterior wall materials; and vehicle components such as interior and exterior materials for vehicles, because the resulting molded products have excellent scratch resistance, impact resistance, and product processability.

[0480] Explanation of symbols

[0481] 1 Test piece

[0482] 2 Friction and wear treatment unit

[0483] 3 Center of the test piece

[0484] 4 Gate.

Claims

1. A resin composition comprising: a graft copolymer (A), a thermoplastic resin (B) and a fatty acid compound (C), wherein the thermoplastic resin (B) does not include the graft copolymer (A) and the polylactic acid polymer (D).

2. The resin composition according to claim 1, wherein the graft copolymer (A) is obtained by graft polymerization of a monomer and a rubber polymer. The rubber polymer includes at least one selected from the group consisting of a composite rubber containing polyorganosiloxane rubber and acrylic rubber, a diene rubber, and an acrylic rubber. The monomer includes a vinyl monomer. The resin composition according to claim 1 or 2, wherein the graft copolymer (A) contains a silicone-based component. 4 . The resin composition according to claim 1 , wherein the thermoplastic resin (B) comprises a (meth)acrylic polymer (B1). The resin composition according to any one of claims 1 to 4, wherein the fatty acid compound (C) comprises at least one selected from the group consisting of saturated fatty acid amide compounds, unsaturated fatty acid amide compounds, bisfatty acid amide compounds and hydroxymethyl fatty acid amide compounds. The resin composition according to claim 5 , wherein the fatty acid compound (C) comprises a fatty acid amide compound. 7 . The resin composition according to claim 6 , wherein the fatty acid amide compound comprises at least one selected from the group consisting of lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide and hydroxymethylstearic acid amide. 8 . The resin composition according to claim 1 , further comprising a polylactic acid-based polymer (D). 9 . The resin composition according to claim 1 , wherein the content of the graft copolymer (A) is 10 to 80% by mass based on the total mass of the resin composition. 10 . The resin composition according to claim 1 , wherein the content of the thermoplastic resin (B) is 10 to 80% by mass based on the total mass of the resin composition. 11 . The resin composition according to claim 1 , wherein the content of the fatty acid compound (C) is 1 to 20% by mass relative to the total mass of the resin composition.

12. The resin composition according to any one of claims 1 to 11, further comprising a polylactic acid polymer (D), The content of the polylactic acid polymer (D) is 1 to 50% by mass based on the total mass of the resin composition. 13 . The resin composition according to claim 1 , wherein the graft copolymer (A) has a gel content of 40% by mass or more and 99% by mass or less.

14. A resin composition comprising more than 45 parts by mass and less than 110 parts by mass of a graft copolymer (A) obtained by graft polymerization of a vinyl monomer and a rubber polymer, relative to a total of 100 parts by mass of a polylactic acid polymer (D) and a (meth) acrylic polymer (B1) containing methyl methacrylate monomer units, wherein the graft copolymer (A) is obtained by graft polymerization of a vinyl monomer (a2) and a rubber polymer (A1) selected from at least one of polyorganosiloxane-acrylic rubber, a diene rubber and an acrylic rubber. 15 . The resin composition according to claim 14 , comprising 65 parts by mass or more and 95 parts by mass or less of the graft copolymer (A) based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1). 16 . The resin composition according to claim 14 , wherein the polyorganosiloxane-acrylic rubber is a composite rubber comprising polyorganosiloxane and an alkyl acrylate rubber. 17 . The resin composition according to claim 14 , wherein a composition ratio of the polylactic acid polymer (D) to the (meth)acrylic polymer (B1) is 1 / 99 to 99 / 1 in terms of mass ratio. 18 . The resin composition according to claim 14 , wherein a composition ratio of the polylactic acid polymer (D) to the (meth)acrylic polymer (B1) is 5 / 95 to 50 / 50 in terms of mass ratio.

19. The resin composition according to any one of claims 14 to 18, which contains 30% by mass or more and 70% by mass or less of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1) in total, and 30% by mass or more and 70% by mass or less of the graft copolymer (A), relative to the total mass of the resin composition. 20 . The resin composition according to claim 14 , wherein the (meth)acrylic polymer (B1) contains 50% by mass or more of a methyl methacrylate monomer unit. 21 . The resin composition according to claim 14 , further comprising a fatty acid compound (C).

22. The resin composition according to claim 21, wherein the fatty acid compound (C) comprises a compound represented by the following general formula (i) as a main component, R-CONH2(i) In the formula, R is a hydrocarbon group having 10 to 25 carbon atoms which may have a substituent. 23 . The resin composition according to claim 21 , wherein the fatty acid compound (C) contains at least one selected from stearic acid amide and palmitic acid amide as a main component. The resin composition according to any one of claims 21 to 23, comprising 0.01 parts by mass or more and 10 parts by mass or less of the fatty acid compound (C) based on 100 parts by mass of the total of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1).

25. The resin composition according to any one of claims 14 to 24, wherein the refractive index Rc of the graft copolymer (A) and the total refractive index Rab of the polylactic acid polymer (D) and the (meth)acrylic polymer (B1) satisfy the following formula (1A), -0.03≤Rc-Rab≤+0.03···Formula (1A). 26 . The resin composition according to claim 14 , wherein the content of the crosslinkable monomer is 0.3 to 10% by mass in 100% by mass of the total monomers constituting the rubber polymer (A1).

27. A resin composition comprising: a graft copolymer (A) containing an organosilicon-based component, a thermoplastic resin (B) and a fatty acid compound (C). 28 . The resin composition according to claim 27 , wherein the graft copolymer (A) is a graft copolymer obtained by graft-polymerizing a monomer containing a (meth)acrylate compound and a composite rubber containing polyorganosiloxane and an alkyl acrylate rubber. 29 . The resin composition according to claim 27 , wherein the fatty acid compound (C) has a melting point of 90° C. or higher. 30 . The resin composition according to claim 27 , wherein the fatty acid compound (C) has a 10% weight loss temperature of 350° C. or less. 31 . The resin composition according to claim 27 , wherein the fatty acid compound (C) comprises a fatty acid amide as a main component.

32. The resin composition according to claim 31, wherein the fatty acid amide is represented by the following general formula (i): R-CONH2(i) In the formula, R is a hydrocarbon group having 10 to 25 carbon atoms which may have a substituent. 33 . The resin composition according to claim 27 , wherein the thermoplastic resin (B) comprises a (meth)acrylate polymer having a repeating unit derived from a (meth)acrylate monomer. 34 . The resin composition according to claim 33 , wherein the (meth)acrylate polymer comprises 80% by mass or more of repeating units derived from a (meth)acrylate monomer relative to 100% by mass of the total mass of the (meth)acrylate polymer.

35. The resin composition according to any one of claims 27 to 34, wherein the graft copolymer (A) is a graft copolymer formed by graft polymerization of 30 to 70 parts by mass of a monomer containing a (meth)acrylate compound and 30 to 70 parts by mass of a composite rubber, wherein the composite rubber contains 1 to 20% by mass of a polysiloxane and 80 to 99% by mass of an alkyl acrylate rubber. 36 . The resin composition according to claim 27 , wherein the resin composition has a gel content of 1% by mass or more. The resin composition according to claim 36 , wherein the gel content of the resin composition is 35% by mass or less.

38. The resin composition according to any one of claims 27 to 37, wherein the resin composition contains a graft copolymer (A) at a content ratio of 1 mass % to 50 mass % and a thermoplastic resin (B) at a content ratio of 50 mass % to 99 mass % relative to the total mass (100 mass %) of the resin composition. 39 . The resin composition according to claim 27 , comprising a fatty acid compound (C) at a content ratio of 0.01% by mass to 10% by mass based on 100% by mass of the total mass of the resin composition. 40 . A molded article comprising the resin composition according to claim 1 .

Citation Information

Patent Citations

  • Production of high-molecular weight polylactide

    JP1984096123A

  • Lactic acid-type polymer composition

    JP1994184417A

  • Impact resistant thermoplastic resin composition

    JP1995025973B2

  • Production of polyhydroxycarboxylic acid

    JP1995033861A

  • Thermoplastic resin composition

    JP1999100484A